Hydrodynamic classification of a binary density feed with no by-pass - D. Awuye; M. Amosah; J.B. Starrett; A.F.D.V. Rodrigues; K.P. Galvin (Minerals Engineering, 2026)

Fungal Extracellular Vesicles are Recoverable Across Variable Ultracentrifugation Speeds but Display Species-specific Profiles of Sedimentation - Luisa J. Jozefowicz; Bárbara T. Bezerra; Eva Veres; Zóra Szilovics; Cássia M. Souza; Amanda C. Camillo-Andrade; Hellen G. G. Santos; Paulo C. Carvalho; Marlon D. M. Santos; Flavia C. G. Reis; Attila Gacser; Marcio L. Rodrigues (The Journal of Membrane Biology, 2026)

Molecular surveillance of Bordetella pertussis during the 2024 outbreak in Southeast Brazil: allelic profiles and comparison to vaccine strain - Thiago J. Sousa; Felipe D. Gatti; Joana Z. Nodari; Gabriela C. de Mendonça; Anna Clara G. Có; Thabata C. D. Damasceno; Nayara C. Silva; Lílian S. Lavagnoli; Danielle G. P. Lyra; Jaqueline P. Goulart; Rodrigo Ribeiro-Rodrigues (Brazilian Journal of Microbiology, 2026)

Acinetobacter venetianus AMO1502: a strain isolated from an oil spill capable of degrading diesel and producing active surface compounds - Marcelo Pereira de Oliveira; Alan Portal D’Almeida; Tiago Lima de Albuquerque; Vânia Maria Maciel Melo; Tigressa Helena Soares Rodrigues; Maria Valderez Ponte Rocha (Brazilian Journal of Microbiology, 2026)

Invading brown bullhead catfish (Ameiurus nebulosus) show thermal niche rigidity and benthic niche plasticity: implications for management - Paul J. Blanchfield; Tazi H. Rodrigues; Calum MacNeil; Simon D. Stewart; Finnbar Lee; Brendan J. Hicks; Shane Grayling; Soweeta Fort-D’Ath; Matthew J. Prentice; Cindy Baker; Peter Williams; Robin J.P. Holmes (Biological Invasions, 2026)

Antibiofilm efficacy of zwitterionic 2-methacryloloxyethyl phosphorylcholine (MPC) polymer coatings against Vibrio fischeri - Murchana Sarma; Ryan P.O’ Hara; Ashfaqul Hoque Khadem; Manas D. Warke; Lihua Lou; Ayse Asatekin; Debora F. Rodrigues (Water Research, 2026)

Biostratigraphy and taphonomic characterization of Moscovian conodonts from Piauí Formation, Parnaíba Basin - Sanmya Karolyne Rodrigues Dias; Martín A. León-Caffroni; Maria D. Traslaviña-Bueno; Andrés Felipe Rojas Mantilla; Ana K. Scomazzon; Sara Nascimento; Paulo A. Souza; Renato Sol Paiva de Medeiros; Jairo Gabriel da Silva Nascimento (Marine Micropaleontology, 2026)

Fatty acid composition and gene expression involved in lipid metabolism from Nelore and Rubia Gallega x Nelore cattle - Adrielle M. Ferrinho; Fabio Luis Henrique; Gabriella Vespe de Moura; Taiane da Silva Martins; Julian Muñoz; Lenise F. Mueller; Pollyana Leite Matioli; Tamyres Rodrigues de Amorim; Alessandra Bridi; Mirele D. Poleti; Juliano Coelho da Silveira; João Negrão; et al. (Livestock Science, 2026)

128 Assessment of pulsing and extrusion dynamics in vitrified equine ICSI embryos under different warming protocols - C.Z. Rodrigues; V.K. Lindsay; C.T.C. Okada; G.P. Correa; M. Azevedo; D. Rossety; C.R. Neto; G.D. Catandi (Journal of Equine Veterinary Science, 2026)

Local structure of trace elements in basaltic glass up to Earth's lower mantle pressures with implications for melt densification and element partitioning - Georgii Kovalskii; Angelika D. Rosa; Olivier Mathon; Wolfgang Morgenroth; Guillaume Morard; Lea Pennacchioni; João Elias Figueiredo Soares Rodrigues; Max Wilke (Chemical Geology, 2026)

Beyond Tubipora musica: Phylogenomics unveils the overlooked diversity and endemism of the hermatypic octocoral genus Tubipora - Laura Macrina; Tullia I. Terraneo; Catherine S. McFadden; Andrea Sabino; Nicolas Oury; Federica Barreca; Silvia Vicario; Kaveh Samimi-Namin; Daniel Knop; Mattie Rodrigue; Vincent Pieribone; Andrew H. Baird; et al. (Molecular Phylogenetics and Evolution, 2026)

Testicular cryopreservation of prepubertal and adult Morada Nova rams: Slow freezing versus vitrification - R.H. Celiz; D.D. Guerreiro; D.C.C. Brito; M.A.S. Novaes; L.V.S. Ñaupas; N.A.R. Sá; G.J.Q. Palomino; F.D.R. Gomes; A.C.A. Ferreira; T.G. Mbemya; C.C.L. Fernandes; L.A.L. Rufino; et al. (Animal Reproduction Science, 2026)

Free-ranging dog’s effects on temporal activity pattern of prey species in areas of Cerrado and Atlantic Forest, Brazil - Letícia Rodrigues Moretto; Bárbara Mitsuko Zukeram Fujioka; Letícia Vitória da Silva; Natalie Olifiers; Letícia Lütke Riski; Paulo Sérgio D’Andrea; Alan Rodrigo Panosso; Roland Kays; Viviane Brito Dias; Rita Bianchi (Biodiversity and Conservation, 2026)

Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

Reproductive toxicity induced by a repeated 28-day oral exposure to a commercial mixture of the herbicides S-metolachlor and flumioxazin in male rats - Renata K. Carvalho; Diego S. Reis; Ana Luísa G. Santiago; Bruna M. Rodrigues; Jacqueline A. Leite; Walter D. Júnior; Virgínia Damin; Monica L. Andersen; Maingredy R. Souza; Paulo C. Ghedini; Hericles M. Campos; Daniela M. Silva; et al. (Chemico-Biological Interactions, 2026)

Effect of supplementation with different trace minerals sources and fibrolytic enzyme on the productive and reproductive performance of Nellore cows on pasture - Keuven S. Nascimento; Amanda C. M. Queiroz; Aline N. Rodrigues; Luiz F. Costa e Silva; Carlos R. Zilioti; James E. Pettigrew; Rodrigo S. Marques; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2026)

Anti-inflammatory potential of the CISACN adduct in LPS-induced murine models - Louise M. de Lima; Francisco A. A. F. Gadelha; Laércia K. D. Paiva Ferreira; Cosmo I. D. Vieira; João B. de Oliveira; Larissa A. M. Paiva Ferreira; Matheus Victor de Souza Laurentino; Bruno Vinícius da Silva Moura; Teresa Carolliny M. L. Rodrigues; Tayná R. Olegário; Luciana Scotti; Marcus T. Scotti; et al. (Inflammopharmacology, 2026)

Multidrug-resistant Pseudomonas aeruginosa in ICU patients and hospital surfaces: β-lactamase burden, biofilm formation and clonal spread - Marcos Eduardo Passos da Silva; Luccas Manoel de Melo Suica; Renata Santos Rodrigues; Márlon Grégori Flôres Custódio; Valcimar Batista Ferreira; Leilane da Silva Pontes; Ivson Cassiano de Oliveira Santos; Bruno Rocha Pribul; Núcia Cristiane da Silva Lima; Izabelly Vitória Gotara Ramos; Anjo Gabriel Carvalho; Mayra Gyovana Leite Belém; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Expert consensus on passive heating interventions to promote skeletal muscle strength and mass: a delphi study - Elisa Lemos; Ian B. Stewart; Patrick Rodrigues; Shawnda A. Morrison; Lee Wharton; Christopher J. Tyler; Stephen S. Cheung; Sebastian Racinais; Ralph J. F. H. Gordon; Alex Lloyd; Julien D. Périard; Katsumasa Goto; et al. (European Journal of Applied Physiology, 2026)
Purpose Passive heating has emerged as a potential non‑exercise method to support muscle strength and mass, but its application is limited by inconsistent protocols and unclear dosage and safety guidelines. This study used a Delphi methodology to establish expert consensus on key parameters for passive heating interventions targeting neuromuscular and muscle morphology outcomes. Methods An international panel of academic experts (≥ 3 peer‑reviewed publications in passive heating and neuromuscular function) completed a two‑round Delphi process. Round 1 gathered open‑ended responses on passive heating strategies, intervention targets, and safety. In Round 2, experts ranked the importance of generated statements. Consensus was defined as ≥ 70% ranking a statement as either first or second in importance. Results Eleven experts completed Round 1 and ten in Round 2. From 177 qualitative responses, 130 statements were evaluated, with 11 reaching consensus (80–100% agreement; interquartile range = 0–1). Hot‑water immersion was prioritised as the most optimal passive heating modality. Experts agreed on targeting muscle temperatures of 39–40 °C, ~ 60-minute session durations, and once‑daily exposure as key intervention parameters. Strong consensus was also reached for monitoring core temperature and cardiovascular strain (e.g., heart rate, blood pressure) to ensure participant safety. No consensus was reached on a single target population or the total intervention duration. Conclusion This Delphi study provides a consensus‑based framework outlining key parameters and safety considerations for passive heating interventions. These findings do not establish efficacy but identify priority variables to inform future experimental research and cautious translation into applied and clinical contexts.

Monte San Nicola (Sicily): Gelasian GSSP and base Quaternary/Pleistocene - L. Capraro; S. Bonomo; A. Incarbona; F.J. Hilgen; E. Zanola; A. Di Stefano; F. Dela Pierre; S. Ferraro; P. Ferretti; E. Fornaciari; S. Galeotti; P. Macrì; et al. (Quaternary Science Reviews, 2026)

Sewage sludge biochar-based fertilizer enriched with K-bearing silicate agrominerals and oxalic acid: physicochemical characterization and carbon stability - Marcela Granato Barbosa dos Santos; José Ferreira Lustosa Filho; Camila Rodrigues Costa; Beatriz Carvalho Lima; Maíra Lopes D'Ávila; Sérgio Sirilo de Oliveira; Gilberto de Oliveira Mendes; Éder de Souza Martins; Giuliano Marchi; Cícero Célio de Figueiredo (Journal of Environmental Management, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Conversion of MDF waste into CoCl2-functionalized activated carbon for enhanced phosphate removal from landfill leachate - A. G. dos Santos; L. C. S. Coelho; D. A. Bertuol; M. A. S. Rodrigues; E. H. Tanabe (International Journal of Environmental Science and Technology, 2026)

Brazil as a Global Leader in Soybean Production: Historical Trends, Current Status, and Future Perspectives - Grazielle Rodrigues Araujo; Felipe Lopes da Silva; Fernado S. Adegas; Edivaldo D. Velini; Ricardo Alcántara-de la Cruz (International Journal of Plant Production, 2026)
Soybean ( Glycine max L.) is the most widely cultivated oilseed globally due to its nutritional value, versatility, and economic importance. It accounts for nearly 25% of global vegetable oil production and is a key component in animal feed, making it strategic for food and energy security. Brazil has emerged as the world leader in production and exports, contributing ~40% of the 2024/25 harvest with approximately 171.5 million tons over ~47.4 million ha. This expansion has been driven by public policies, research investments, territorial expansion, and the widespread adoption of genetically modified (GM) varieties, now covering over 99% of the cultivated area. The transformation of the Cerrado into a major agricultural frontier, combined with technological advances, has resulted in substantial increases in area, production, and yield (~3.6 t ha − 1 in 2024/25). Despite these gains, yields remain far below the crop’s potential (>8.9 t ha − 1 in experimental fields), highlighting the presence of a persistent yield gap between current and attainable productivity levels. This review synthesizes the historical evolution of soybean production in Brazil and examines the main production drivers, structural constraints, and emerging innovation pathways shaping future productivity. Particular attention is given to the challenges associated with climate variability, environmental regulation, and increasing global demand for sustainable supply chains. The analysis highlights that future production gains will depend on the transition from expansion-driven growth to sustainable intensification, supported by technological innovation, improved management strategies, and effective governance.

Ex vivo validation of osteogenic efficacy in a bioceramic dual drug-delivery system - Miguel A. Rodrigues; Liliana Grenho; Rita Araújo; João P. Borges; Maria H. Fernandes; Pedro S. Gomes; José D. Santos; Maria A. Lopes (Drug Delivery and Translational Research, 2026)

WITHDRAWN: Inflammatory markers levels and clinical characteristics in COVID-19 susceptibility and severity: A cross-sectional multicentric study - Lucas C. Pedro; Camila O. Arent; Flávia S. Niero; Caion A. Rodrigues; Margarete D. Bagatini; Gabriela G. de Oliveira; Zuleide Maria Ignácio; Larissa Joaquim; Fabricia Petronilho; João Quevedo; Alexandra I. Zugno; Luciane B. Ceretta; et al. (Next Research, 2026)

Cold plasma as a sustainable strategy for enzyme inhibition in plant diseases and postharvest losses: a review - Thaís Caroline Buttow Rigolon; Gabriel Oliveira Horta; Diego Pádua de Almeida; Paulo Cesar Stringheta; Evandro Martins; Lêda Rita D'Antonino Faroni; Ernandes Rodrigues de Alencar; Pedro Henrique Campelo (Journal of Stored Products Research, 2026)

Lung deposition, health risks, and composition of PM2.5 collected in an industrial area in Southern Brazil - Camila N. Farias; Gabriel D. Barp; Eduardo Karnopp; Katarina O. Rodrigues; Marcos A. Hortellani; Jéssica C. Santos-Silva; Jorge E.S. Sarkis; Mariane Bonatti-Chaves; Sandra H.W. Medeiros; Pérola C. Vasconcellos (Atmospheric Pollution Research, 2026)

Synthesis and application of silver-doped glass waste pellets for drinking water treatment - J. S. C. Vieira; J. D. A. do Ano; A. R. Pereira; A. da Costa Reis; F. W. Carvalho; I. A. da Silva; M. R. de Melo Rodrigues; E. M. V. de Carvalho; D. L. P. Macuvele; G. J. Muchave (International Journal of Environmental Science and Technology, 2026)

The emergence of pathogens on fish in an impacted estuary and the role of non‐native piranhas in a potential bacterial infectious outbreak - Ryan Andrades; Helder C. Guabiroba; Kathiani V. Bastos; Vítor L. A. Rodrigues; Marcelo R. D. Santos; Clarisse M. Arpini; Mayra Cunha Flecher; Helen A. Pichler; Ciro C. Vilar; Maurício Hostim‐Silva; Jean‐Christophe Joyeux (Journal of Fish Biology, 2026)
As many tropical aquatic ecosystems worldwide, the Doce River estuary (DRE, southeastern Brazil) has increasingly faced multiple anthropogenic threats, including deforestation, mining, species introduction and water management. The 2015 collapse of the Fundão iron ore tailings dam severely changed water properties and increased heavy metal concentration in sediment. However, the potential synergistic effects of the observed threats on fish populations remain largely unknown. After detecting an elevated number of fin lesions in DRE fishes, we used the catfish Genidens genidens (Cuvier, 1829) to investigate whether such mutilations originated from fin‐nipping by non‐native piranha or emerged as a result of fin rot disease through bacterial infection. One third of the examined individuals had fin lesions in the DRE, whereas no conspecific exhibited such lesions in two control estuaries where piranhas are absent; lesions were restricted to the caudal fin, a region known to be targeted by fin‐nipping piranhas. Independently of the presence of fin lesion, culture of fins and livers indicated higher prevalence and variety of bacterial strains in DRE individuals than in a control area. Piranhas likely contribute to the fin lesions in DRE fishes. However, the higher prevalence and variety of bacterial pathogens as well as of liver and kidney disorders identified in fin‐healthy and mutilated fishes of the DRE suggest that the heavily metal‐polluted conditions in the DRE may be associated with the emergence of bacterial infections in fish.

Chemical and Bioactivity Profiling of the Invasive Macroalga Rugulopteryx okamurae Collected in Southern Portugal Supporting Biotechnological Valorisation Approaches - Amandine D’Unienville; Lucas Lasnel; Wadi Macquigneau; Riccardo Trentin; Adriana C. S. Pais; Maria João Rodrigues; Sónia A. O. Santos; Luísa Custódio (Journal of Marine Science and Engineering, 2026)
The invasive brown macroalga Rugulopteryx okamurae has rapidly expanded across the Mediterranean–Atlantic region, generating severe ecological impacts. Nevertheless, the considerable amount of biomass available creates opportunities for valorisation within circular bioeconomy frameworks. This study provides an integrated characterization of the chemical profile and bioactivities of freshly collected floating biomass of R. okamurae from southern Portugal. Proximate composition was determined, and lipophilic (hexane) and hydrophilic (water) extracts were analyzed by GC–MS and spectrophotometric methods. Antioxidant activity was assessed using complementary radical-scavenging, reducing power, and metal-chelation assays, and enzyme inhibition was evaluated against targets associated with neurodegenerative, metabolic, and dermatological disorders. The lipophilic fraction was dominated by long-chain alkanes (≈101 mg/g extract) and sterols, particularly fucosterol (≈43 mg/g extract), but exhibited low radical-scavenging capacity (no EC50 reached in DPPH or ABTS assays), and no relevant enzyme inhibition. In contrast, the water extract contained measurable phlorotannins (6.61 mg PGE/g extract) and showed moderate antioxidant (ABTS: EC50 = 5.17 mg/mL; FRAP: EC50 = 0.78 mg/mL) and enzyme inhibition activities (BChE: IC50 = 5.17 mg/mL; tyrosinase: IC50 = 0.78 mg/mL). Compared with previous studies on R. okamurae, this work applies a systematic fractionation of biomass from southern Portugal into polar and non-polar fractions and, for the first time, correlates the resulting detailed chemical profiles with multiple bioactivities. This approach revealed a clear functional differentiation between fractions, with bioactivity being mainly associated with polar metabolites. Overall, these findings highlight the value of structured extraction strategies for biomass valorisation and support the sustainable management of R. okamurae.

Efficacy of ozone in bifenthrin degradation and its impact on the quality of common beans (Phaseolus vulgaris L.) - Carlos Henrique de Oliveira Paz; Lêda Rita D'Antonino Faroni; Alessandra Aparecida Zinato Rodrigues; Eugénio da Piedade Edmundo Sitoe; Maria Eliana Lopes Ribeiro de Queiroz; Marcus Vinícius de Assis Silva; Ernandes Rodrigues de Alencar; Carollayne Gonçalves Magalhães (Food Control, 2026)

Melatonin Alleviates Aluminum Toxicity in Pfaffia glomerata by Modulating Tolerance Mechanisms - Michelle M. V. Almeida; Juliane M. Henschel; Tatiane D. Silva; Luiza E. G. Monteiro; Mateus S. Rodrigues; Tadeu R. Oliveira; Auxiliadora O. Martins; Sérgio H. S. Felipe; Evandro A. Fortini; Elyabe M. Matos; Lyderson F. Viccini; Diego S. Batista; et al. (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is the main factor limiting agricultural production in acidic soils around the world. In this scenario, melatonin (MET) has emerged as a promising approach to alleviate Al toxicity. Thus, we investigated morphophysiological responses of Pfaffia glomerata (Spreng.) Pedersen, a medicinal plant, to Al toxicity and MET application. Plants were grown in vitro for 40 days in MS medium (control) supplemented with Al, MET, and Al + MET. Aluminum had genotoxic effects, inducing DNA damages and endoreduplication, which resulted in growth arrest, mainly in roots. Al also decreased the photosynthetic rate and the contents of pigments, carbohydrates, amino acids, and proteins. On the other hand, all these effects were improved in plants supplemented with MET. This is supported by the up-accumulation of proteins involved in organic acids exudation (AHA2), photosynthesis (transketolase, rubisco activase, and photosystem I P700 apoprotein A2), amino acid biosynthesis (chorismate synthase 1 and aspartokinase/homoserine dehydrogenase), and cell expansion and differentiation (rough sheath 2, beta tubulin b6, and tubulin beta chain-like). Moreover, MET enhanced CAT, SOD, and GABA, reinforcing its antioxidant role and reducing DNA damage and endoreduplication, which preserved QC identity and root elongation. Al toxicity impaired growth and carbon–nitrogen metabolism, whereas MET mitigated these effects by boosting photosynthesis, antioxidant defenses, and Al sequestration, decreasing Al adherence to roots. Thus, MET serves as a protective molecule against Al toxicity in P. glomerata .

Quantification and characterization of collagen in experimentally induced wounds treated with different types of platelet-rich plasma gel - G. Haro de Melo; F. M. Moreira; G. G. Mori; L. F. Bento; D. V. Barrionuevo; C. B. Laposy; R. Giuffrida; A. F. F. Rodrigues; G. A. T. Ozaki; D. A. F. da Silva; F. L. Pacagnelli; R. M. B. Nogueira (Cell and Tissue Banking, 2026)
Due to its high concentration of growth factors, platelet-rich plasma (PRP) has become the subject of much research, either as an isolated or adjuvant treatment for wound repair. The fractal dimension has been used as an innovative method for the characterization and quantification of tissue structural alterations without any interference from the evaluator. The objective of this study was characterizing collagen types I and III in experimentally induced wounds and treated with different PRP sources by means of fractal dimension and other histological analyzes using blades stained with picrocirius-red and hematoxylin-eosin (HE). In statistical analysis, the variables presented a non-parametric distribution; thus, Mann-Whitney and Kruskall-Wallis tests ( p < 0,05) were performed using the Student-Newman-Keuls method. It was observed an increase of the collagen fibers by measuring the area with Threshold Color in the different treatments, especially with autologous PRP ( p = 0.009) and heterologous PRP ( p = 0.016). The fractal dimension of type I collagen had a significant increase for the autologous group ( p = 0.028) in relation to the control, but, on average ( p < 0.05), type III collagen was higher than type I. Fractal dimension was efficient to separately characterize type I and type III collagen fibers. In this study, collagenization was higher in autologous when compared to heterologous and homologous PRP treatments.

Erratum to “A call for CARE in animal behaviour: an holistic ethical research framework” [Animal Behaviour 231 (2026) 123428] - Gal Badihi; Jennifer Taylor-O’Connor; Gabriela Bezerra de Melo Daly; Viola Komeda; Sophia Daoudi-Simison; Evelina D. Rodrigues; Michael M. Webster; Drew M. Altschul; Catherine Hobaiter; Charlotte Wiltshire; Harmonie Klein; Elodie Freymann; et al. (Animal Behaviour, 2026)

Forest residue removal undermines soil health and micronutrient transfer to trees, compromising sustainable productivity of Eucalyptus plantations - Antonio L. Florentino; Nariane de Andrade; Nikolas S. Mateus; Bruna E. Schiebelbein; Adam C. Rodrigues; Liamara S. Masullo; Alexandre V. Ferraz; Eduardo Mariano; Fernando D. Andreote; Carlos E.P. Cerri; Maurício R. Cherubin; Timothy R. Filley; et al. (Soil and Tillage Research, 2026)

Performance analysis and geometric evaluation of galvanized T- and Y-Shapes for earth-air heat exchangers using constructal design - Ana M.B. Domingues; Andre L. Razera; Jairo V.A. Ramalho; Michel K. Rodrigues; Honório J. Fernando; Liércio A. Isoldi; Elizaldo D. dos Santos (Geothermics, 2026)

Rehydrated ground corn silage as alternative to feedlot lambs: feeding behavior and performance - Leandro A. S. da Silva; Cláudia L. S. Lima; Gleidson G. P. de Carvalho; Henry D. R. Alba; Maria L. G. M. L. de Araújo; Cláudia H. da Cruz; Carlindo S. Rodrigues; Dalton H. Pereira; José E. de Freitas Júnior; Manuela S. L. Tosto; Douglas dos S. Pina (Tropical Animal Health and Production, 2026)

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Incorporating statistical uncertainty into metamodel-driven Performance-Based Risk Optimization for seismic design - Isabela D. Rodrigues; Seymour M.J. Spence; André T. Beck (Engineering Structures, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Induction of oxidative stress and functional impairment by Doxorubicin in rat salivary glands - Guilherme Eduardo Rocha Silva; Ana Clara Emilio Padovezi; Renan José Barzotti; Larissa Victorino Sampaio; Rayara Nogueira de Freitas; Cristiane Furuse; Walid D. Fakhouri; Rafael Rodrigues Lima; Mariza Akemi Matsumoto; Antonio Hernandes Chaves-Neto (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A call for CARE in animal behaviour: an holistic ethical research framework - Gal Badihi; Jennifer Taylor-O’Connor; Gabriela Bezerra de Melo Daly; Viola Komeda; Sophia Daoudi-Simison; Evelina D. Rodrigues; Michael M. Webster; Drew M. Altschul; Catherine Hobaiter; Charlotte Wiltshire; Harmonie Klein; Elodie Freymann; et al. (Animal Behaviour, 2026)

Effects of red light-emitting diode therapy in imiquimod-induced psoriasis in mice - Mab P. Corrêa; Rebeca D. Correia-Silva; Diego D. Santos; Nathália Rodrigues-Silva; Pâmela P. Borges; Silvana Sandri; Karin V. Greco; Cristiane D. Gil (Journal of Photochemistry and Photobiology B: Biology, 2026)

Protected areas influence fire regimes globally - A. Cardil; M. Rodrigues; D. Ascoli; M. Ortega; T. Quiñones; M. Erdozain; I. Oliveras Menor; G.L. Spadoni; J. Ramírez; J.R. Molina; F. Mouillot; C.A. Silva; et al. (Journal of Environmental Management, 2026)

Taxonomic update for the giant algal chloroviruses of the family Phycodnaviridae - Rodrigo A. L. Rodrigues; João Victor R. P. Carvalho; Lethícia R. Henriques; David D. Dunigan; James L. Van Etten (Archives of Virology, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Metabolomics uncovers the dual effects of high-pressure and ultra-shear processing in a blended fruit-vegetable juice - Giovana Domeneghini Mercali; Eliseu Rodrigues; Cristian D. Quiroz-Moreno; Sai Sashidhar Guduru; V.M. Balasubramaniam; Jessica Cooperstone (Food Chemistry, 2025)

A new carbon quantum dot obtained from acerola (Malpighia glabra) seed waste and its application as a corrosion inhibitor of mild steel in hydrochloric acid - Victor Magno Paiva; Sanair Massafra de Oliveira; Agnes Candido Teixeira; Jairo Eduardo Leiva Mateus; Clara Muniz da Silva de Almeida; Joyce Rodrigues de Araújo; Marcelo Eduardo Huguenin Maia da Costa; Natasha Midori Suguihiro; Eliane D'Elia (Biomass and Bioenergy, 2025)

SpiderATLAS : A Database of Spider Traits and Distributions in the Brazilian Atlantic Forest - Gabriel X. Boldorini; Paulo M. Martins; Antonio D. Brescovit; Adalberto J. Santos; Leonardo S. Carvalho; Ubirajara Oliveira; Philip Russo; Joyce C. B. Brito; Aparecida P. Barbosa; André Celso Bezerra Rodrigues; Aníbal Silva Cantalice; Arthur A. B. Rodrigues; et al. (Journal of Biogeography, 2025)
Aim Biodiversity shortfalls related to limited knowledge about geographic distribution (Wallacean) and species traits (Raunkiæran) are extremely common in many animal groups and perhaps more evident in invertebrate groups such as spiders. This lack of knowledge could present challenges for researchers investigating the response and effects of spiders along large spatial scales, particularly in the Global South. The aim of the SpiderATLAS is to facilitate research that links macroecology, biogeography, trait‐based ecology and global change biology. Location Brazilian Atlantic Forest, spanning virtually the entire eastern coastline of Brazil, encompassing 1,620,000 km 2 , 30 degrees of latitude (3° 42′ S to 33° 31′ S), and 22 degrees of longitude (34° 50′ W to 56° 45′ W). Taxon Spiders (Class Araneae), including 1648 species from 63 families. Methods We compiled the spatial distribution (i.e., occurrence data) and data on morphological characteristics and derived traits for spider species from species descriptions, taxonomic revisions and personal collection. Species occurrences were extracted from several data sources spanning from the 1880s to 2023. Data on the morphological traits of species were compiled from taxonomic and diversity inventory papers published between 1833 and 2024. Results We provide 9369 georeferenced point locations and six morphological traits (body length, prosoma length, prosoma width, prosoma height, femur I length, and patella I length) for 1648 spider species. Most data are available for females and males. The dataset and code are available to download from Dryad, World Spider Trait database, and the ZooTraits app. Main Conclusions The SpiderATLAS can be useful to access information on the distribution and traits of spiders, contributing to the development of macroecological, biogeographical and trait‐based ecology. This dataset can also facilitate the biodiversity conservation of one of the most abundant and important arthropod predators on the planet, in a biodiversity hotspot.

Numerical and fracture mechanics-based simulations of brittle failure in dowelled timber connections under in-plane multiaxial forces and bending moment - Caroline D. Aquino; Michael Schweigler; Leonardo G. Rodrigues; Luis C.M. da Silva; Jorge M. Branco; Thomas K. Bader (Engineering Structures, 2025)

A highly efficient platform for Arabidopsis hairy root induction using Agrobacterium strain K599 - Savio D. Rodrigues; Dries Delmotte; Gianni De Coster; Ona Sweron; Eveline Van den Steen; Jonas De Saeger; Laurens Pauwels; Barbara De Coninck (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Aerobic exercise training combined with enalapril treatment improves obesity-induced brown adipose tissue whitening - Gabriela Rodrigues Medeiros; Luiza França Losito; Ana Beatriz Proença; Guilherme Santos Reis; Nathalia Silva Carlos Oliveira; D’Angelo Carlo Magliano; Beatriz Alexandre-Santos; Antonio Claudio Lucas Nóbrega; Eliete Dalla Corte Frantz (Journal of Physiology and Biochemistry, 2025)

The Functional Role of Specific Habitats for the Daily Routine of Juvenile Spoonbills in Protected Coastal Wetlands - Manuela S. Rodrigues; Pedro M. Araújo; Jaime A. Ramos; Pedro C. Rodrigues; Afonso D. Rocha; João P. Silva; José A. Alves (Estuaries and Coasts, 2025)
Wetlands are decreasing globally and species that depend on these habitats must adjust their behaviour or may face population declines. Protected wetlands designed for the conservation of certain species may fail to meet their objectives if habitats critical for specific behaviours are degraded, even if other habitats remain unaffected. It is therefore important to better understand the functional role of specific coastal wetland habitats and when species need them. We investigated the behaviour of juvenile spoonbills ( Platalea leucorodia ) from two Portuguese protected wetlands: the Tagus estuary and Ria Formosa coastal lagoon. Forty-four juvenile spoonbills were equipped with GPS/GSM tags with a 3-axial accelerometer, which allowed integrating spatially explicit behaviour with land use data. We then explored how habitat use changes with diel and tidal cycles within these dynamic landscapes and assessed the functional role of habitats. Juvenile spoonbills vary their daily routines according to the composition of habitats in their natal wetland, with the diel cycle being more influential in the Tagus estuary, while in Ria Formosa both cycles (diel and tidal) were of similar relevance. Habitats were used differently within the study areas: intertidal flats accounted for 62.09% of feeding activity in Ria Formosa versus 47.16% in the Tagus estuary, where rice fields represented the highest feeding percentage (52.27%). This work highlights the need for species- and site-specific studies and can serve as a template for understanding habitat use by other species (or different life stages) to support the development of targeted conservation measures.

Ancient Introgression Explains Mitochondrial Genome Capture and Mitonuclear Discordance Among South American Collared Tropidurus Lizards - Matheus M. A. Salles; André L. G. Carvalho; Adam D. Leaché; Nicolas Martinez; Frederick Bauer; Martha Motte; Viviana Espínola; Miguel T. Rodrigues; Carla Piantoni; Marcio R. Pie; André Olivotto; Guarino R. Colli; et al. (Molecular Ecology, 2025)
Mitonuclear discordance—evolutionary discrepancies between mitochondrial and nuclear DNA phylogenies—can arise from various factors, including introgression, incomplete lineage sorting, recent or ancient demographic fluctuations, sex‐biased dispersal asymmetries, among others. Understanding this phenomenon is crucial for accurately reconstructing evolutionary histories, as failing to account for discordance can lead to misinterpretations of species boundaries, phylogenetic relationships, and historical biogeographic patterns. We investigate the evolutionary drivers of mitonuclear discordance in the Tropidurus spinulosus species group, which contains nine species of lizards inhabiting open tropical and subtropical environments in South America. Using a combination of population genetic and phylogenomic approaches applied to mitochondrial and nuclear data, we identified different instances of gene flow that occurred in ancestral lineages of extant species. Our results point to a complex evolutionary history marked by prolonged isolation between species, demographic fluctuations, and potential episodes of secondary contact with genetic admixture. These conditions likely facilitated mitochondrial genome capture while diluting signals of nuclear introgression. Furthermore, we found no strong evidence supporting incomplete lineage sorting or natural selection as primary drivers of the observed mitonuclear discordance. Therefore, the unveiled patterns are most consistent with neutral demographic processes, coupled with ancient mitochondrial introgression, as the main factors underlying the mismatch between nuclear and mitochondrial phylogenies in this system. Future research could further explore the role of other demographic processes, such as asymmetric sex‐biased dispersal, in shaping these complex evolutionary patterns.

Investigation of PFAS/nPd/μZVI interactions: mechanism, performance, and nPd/μZVI reuse - Raphaël Tur; Stéphanie Betelu; Romain Rodrigues; Stéfan Colombano; Dorian Davarzani; Sébastien Bristeau; Julien Grandclément; Arnaud Perrault; Julie Lions; Eric D. van Hullebusch; Ioannis Ignatiadis (Science of The Total Environment, 2025)

Turning the Tide: Harnessing the Invasive algae Rugulopterix okamurae for Commercial Applications - Amandine D’Unienville; Lucas Lasnel; Wadi Macquigneau; Riccardo Trentin; Maria J. Rodrigues; Luísa Custódio (Phytochemistry Letters, 2025)

The overlooked variables: Slide thickness and 3D tumour heterogeneity on mitotic counts of canine mast cell tumours - P. Faísca; L. Silva; I. Carvalho; J. Santos; J. Catarino; D. Ramilo; P. Rodrigues; A. Gama (Journal of Comparative Pathology, 2025)

Amazonian trees functional adjustments to long term experimental drought are limited and species dependent - Vanessa Negrão-Rodrigues; Paulo Bittencourt; Pablo Sanchez-Martinez; Lucy Rowland; Lion R. Martius; Patrick Meir; Manolo T. Quintilhan; José Roberto V. Aragão; Victor Brigatto; Vinicius D. Oliveira; Peter Groenendijk; Arlete A. Soares; et al. (Flora, 2025)

Combination therapies and novel delivery systems: a new frontier in overcoming TRAIL resistance in gastric cancer - Paul Rodrigues; Abdulrahman T. Ahmed; Majid Jabir; Khetam Habeeb Rasool; Soumya V. Menon; Aryantika Sharma; M. Ravi Kumar; Matheel D. Al-Sabti; Sabrean F. Jawad; Salah Hassan Zain Al-Abdeen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

Unraveling the impact of coffee fermentation: Interactions among processing variables and their effects on sensory quality - Camila Aparecida Lessa Soares; Ernandes Rodrigues de Alencar; Marileusa D. Chiarello; Lívia de Lacerda de Oliveira (Trends in Food Science & Technology, 2025)

CFD modelling of an urban microclimate during a heat wave: Coupling solar radiation and heat transfer - D. Nascimento; A. Ascenso; D. Lopes; M. Lopes; V. Rodrigues (Urban Climate, 2025)

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

Multistage treatment system integrating constructed wetlands and microalgae for wastewater reuse and bioenergy recovery - Gustavo S. Colares; Luana T. Junqueira; Fernanda N. Brum; Romualdo J.C. Wanderley; Tainá Conzatti; Lenin D. Garcia; Lucia H.R. Rodrigues; Carlos A. Lutterbeck; Ênio L. Machado; Odorico Konrad (Journal of Water Process Engineering, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Hyperspectral remote sensing as an environmental plastic pollution detection approach to determine occurrence of microplastics in diverse environments - Zachary K. Holt; Shuhab D. Khan; Debora F. Rodrigues (Environmental Pollution, 2025)

Total nutrient digestibility and small intestine starch digestion in Nellore and Nellore × Angus steers fed whole shelled corn-based diet with or without roughage - Priscilla D. Teixeira; Aline C. Rodrigues; Daniel R. Casagrande; Erick D. Batista; José M. Oliveira; Ana C.O. Santos; Pedro V.R. Paulino; Marcio M. Ladeira (Livestock Science, 2025)

Influence of sugar addition in Kombucha production regarding the beverage effect on human fecal microbiota composition and metabolite profile - Maria de Fátima D. Linhares; Thatyane Vidal Fonteles; Francisca Andrea de Oliveira; Sueli Rodrigues (Food Bioscience, 2025)

Biomass of South Brazilian highland grassland under management with burning and mowing: Characterization of vegetation and feedstock for energy - Taíse Mariano Rodrigues; Martha Andreia Brand; Tássio Dresch Rech; Tiago Celso Baldissera; Cassiano Eduardo Pinto; Fabio Cervo Garagorry; Alexsandro Bayestorff da Cunha; Polliana D'Angelo Rios; Rodrigo Figueiredo Terezo; Giovanna de Oliveira Souza; Lucas de Lima Ribeiro (Biomass and Bioenergy, 2025)

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

Non-targeted metabolomic analysis of field-grown Coffea arabica cultivars reveals distinct leaf metabolic signatures - Jéfyne Campos Carréra; Leonor Guerra-Guimarães; John Charles D’Auria; Luana de Jesus Sartori; Carla Pinheiro; Vânia Aparecida Silva; Margarete Lordelo Volpato; Gladyston Rodrigues Carvalho; Fabio Akira Mori (Theoretical and Experimental Plant Physiology, 2025)
This study conducted a non-targeted metabolomic analysis of five Coffea arabica L. cultivars grown in the field experimental areas of the Cerrado Mineiro (Minas Gerais State, Brazil) to identify their metabolic fingerprints. The five cultivars selected for this study were chosen based on their specific genetic backgrounds and traits, including disease resistance, productivity, and cup quality. A total of 463 metabolic features were detected in the overall C. arabica metabolome, with the major metabolic classes comprising sugars, amino acids, lipids, phenylpropanoids, and phenolic compounds. Among these, 41 metabolites were identified as key discriminators among the five cultivars. Partial least squares discriminant analysis (PLS-DA) revealed distinct metabolic profiles, highlighting ferulic acid, theobromine, octopamine, rosmarinic acid, and gibberellin as key metabolites. These findings emphasize the importance of phenolic compounds and alkaloids in cultivar discrimination. The most relevant metabolic markers associated with environmental stress tolerance suggest their potential as biochemical indicators for selecting resilient cultivars, thereby contributing to coffee breeding programs. Notably, this study is the first documented characterization of the leaf metabolome of field-grown C. arabica cultivars, with Catiguá MG2 emerging as the most distinct. Our findings demonstrate the efficacy of metabolomic fingerprinting via non-targeted metabolomic as a powerful tool for differentiating coffee cultivars and for precision breeding strategies.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Impact of shear stress and moderate electric field on the global metabolic profile of a blended fruit and vegetable juice - Giovana Domeneghini Mercali; Eliseu Rodrigues; Cristian D. Quiroz-Moreno; Sudhir K. Sastry; Jessica Cooperstone (Food Research International, 2025)

Do behavioral attitudes of livestock farmers in Cameroon influence the adoption of insect-based feed? An application of the theory of planned behavior - Ruth T. Nembu; Boris D. Soh Wenda; Hervé K. Mube; Hervé W. Napi; Shaphan Y. Chia; Sali A. Ndindeng; Rodrigue B. Kamga; Dorothy E. Fon (Food and Humanity, 2025)

Estimation of diurnal and nocturnal radiation balance in tropical ecosystems - D. O. Maionchi; I. J. C. de Paulo; S. R. de Paulo; J. B. Marques; A. L. P. Junior; H. J. A. da Silva; R. S. Palácios; T. R. Rodrigues; T. A. dos Santos; A. M. S. Lima; M. S. Biudes; L. Sanches; et al. (Theoretical and Applied Climatology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Tailoring a lignocellulosic biomass to simultaneously enhance N-doping and textural properties of porous carbons designed for effective environmental remediation - Letícia D. Capel; Liriana M. Roveda; Claudio T. Carvalho; Magno A.G. Trindade; Robson M. da Silva; Raphael Rodrigues (Environmental Research, 2025)

Phylogenetic diversity and conservation challenges in Brejos de Altitude: assessing threatened areas of the Brazilian Atlantic Forest - Anderson Silva Pinto; Fernanda Kalina da Silva Monteiro; Erimágna de Morais Rodrigues; D’Ávilla Ruama Fernandes Lopes Gomes; Macelly Correia Medeiros; Sérgio de Faria Lopes (Regional Environmental Change, 2025)

Incorrect Identification in the Marketing of Serrasalmid Fishes: A Threat to Native Species and Productivity in the Aquaculture Industry - Diego G. Martins; Fernanda D. Prado; Ricardo Utsunomia; Diogo Teruo Hashimoto; Caio Augusto Gomes Goes; Fausto Foresti; Carlos Egberto Rodrigues Junior; Fabio Porto-Foresti (Fishes, 2025)
Interspecific hybridization can offer advantages in fish aquaculture by enhancing traits like growth rate and disease resistance. However, improper management can result in heterogeneous breeding stocks, which pose risks if hybrids interbreed with native populations. This can lead to loss of genetic diversity and alterations in population structure. This study aimed to evaluate the prevalence of hybridization within the Brazilian aquaculture industry, focusing on the economically significant Serrasalmid species, such as Piaractus mesopotamicus (pacu), Piaractus brachypomus (pirapitinga), Colossoma macropomum (tambaqui), and their hybrids. Using molecular markers (TROP and APOC SNP markers), 312 individuals from the Companhia de Entrepostos e Armazéns Gerais de São Paulo (CEAGESP), the largest warehouse in Latin America, were assessed. The results revealed that 80% of the samples were misidentified, with a substantial proportion of hybrids (72.12%). Among these hybrids, 71.6% were classified as F1 hybrids, while 28.4% were post-F1 hybrids. These findings highlight the need for improved genetic monitoring and management practices in Brazil’s fish production industry, emphasizing the importance of sustainable practices to ensure the long-term viability of aquaculture while preserving native genetic resources.

Characterization of the lipid profile of the equine sperm plasma membrane - D. Rodrigues; C. Ramires Neto; C. Freitas-Dell'Aqua; K.R. Belaz; D. Zampieri; A. Tata; M.N. Eberlin; F.F. de Souza; F.O. Papa; J.A. Dell'Aqua Júnior (Journal of Equine Veterinary Science, 2025)

Numerical and fracture mechanics-based simulations of brittle failure modes in dowelled timber connections loaded parallel to the grain - Caroline D. Aquino; Michael Schweigler; Leonardo G. Rodrigues; Luis C.M. da Silva; Jorge M. Branco; Thomas K. Bader (Engineering Structures, 2025)

An automated technique and decision support system for lightning early warning - M. A. Alves; B. A. S. Oliveira; D. B. S. Ferreira; A. P. P. Santos; W. F. S. Maia; W. S. Soares; F. P. Silvestrow; L. F. M. Rodrigues; E. L. Daher; O. Pinto (International Journal of Environmental Science and Technology, 2025)

Impact of Drilling Fluids on Borehole Hydraulic Conductivity in Geotechnical Investigations - F. Schnaid; B. A. Rodrigues; D. E. Lourenço; G. M. A. do Patrocínio; S. Maghous; J. L. dos Santos; M. L. P. Alves; R. Fonseca; V. B. de Araújo (Geotechnical and Geological Engineering, 2025)

Ceftazidime-avibactam tolerance and persistence among difficult-to-treat KPC-producing Klebsiella pneumoniae clinical isolates from bloodstream infections - N. Abichabki; G. G. Gaspar; L. R. Bortolato; D. A. F. S. Lima; L. N. Silva; R. H. C. Pocente; J. C. Ferreira; T. C. Ogasawara; D. Pereira; R. R. Guerra; C. Wilhelm; P. Barth; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Landscape influences bat suppression of pine processionary moth: Implications for pest management - A.M. Augusto; S. Pereira; S. Rodrigues; F. Marques; O. Aizpurua; A. Alberdi; G. Jones; O. Razgour; T.A. Marques; D. Russo; H. Rebelo (Journal of Environmental Management, 2025)

Schwann cells exposed to articaine display distinct toxic pathways compared to lidocaine - Gustavo H. Rodrigues da Silva; Luís F. Mendes; Gabriela Geronimo; Ludmilla D. de Moura; Juliana S. Ruas; Roger F. Castilho; Helon G. Cordeiro; Carmen V. Ferreira; Eneida de Paula; Iola F. Duarte (Chemico-Biological Interactions, 2025)

Toxicity of REEs, Th, and U: A Biodisponibility, Cytotoxicity, and Bioaccumulation Assessment in Marine Sediment - Suellen Gerônimo Cordeiro; Ana Cláudia H. Pereira; Denise Coutinho Endringer; Luana Santos Moreira; Maria Tereza W. D. Carneiro; Jefferson Rodrigues de Souza; Geisamanda Pedrini Brandão (Biological Trace Element Research, 2025)

Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

Airborne DNA: State of the art – Established methods and missing pieces in the molecular genetic detection of airborne microorganisms, viruses and plant particles - C.-E. Pogner; C. Antunes; G.P. Apangu; N. Bruffaerts; S. Celenk; A. Cristofori; N. González Roldán; A. Grinn-Gofroń; B. Lara; M. Lika; D. Magyar; M. Martinez-Bracero; et al. (Science of The Total Environment, 2024)

A multicommuted system using bacterial cellulose for urease immobilization and copper (II)-MOF colorimetric sensor for urea spectrophotometric determination in milk - Julyana C. Rodrigues; Caio S. Bezerra; Lidiane M.A. Lima; Danielle D. Neves; Ana Paula S. Paim; Wagner E. Silva; André F. Lavorante (Food Chemistry, 2024)

Dietary supplementation of mineral nanoparticles for channel catfish (Ictalurus punctatus) - Vitor F. Silva; José Luiz P. Mouriño; Maurício L. Martins; Pedro L. P. F. Carvalho; Edgar D. Rodrigues; Delbert M. Gatlin; Matt J. Griffin; Caitlin E. Older; Fernando Y. Yamamoto (Fish Physiology and Biochemistry, 2024)

Polymyxin resistance in Enterobacter cloacae complex in Brazil: phenotypic and molecular characterization - Bianca Santos da Costa; Renata Stavracakis Peixoto; Orlando Carlos da Conceição Neto; Leilane da Silva Pontes; Thamirys Rachel Tavares e Oliveira; Camila Bastos Tavares Teixeira; Ivson Cassiano de Oliveira Santos; Melise Chaves Silveira; Daiana Cristina Silva Rodrigues; Bruno Rocha Pribul; Cláudio Marcos Rocha-de-Souza; Ana Paula D.’Alincourt Carvalho-Assef (Brazilian Journal of Microbiology, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Depth estimation of pre-Kalahari basement in Southern Angola using seismic noise measurements and drill-hole data - J. Carvalho; D. Alves; J. Borges; B. Caldeira; D. Cordeiro; A. Machadinho; A. Oliveira; E.C. Ramalho; J.F. Rodrigues; J.M. Llorente; M. Ditutala; J.L. García-Lobón; et al. (Journal of Applied Geophysics, 2024)

Bisphenol S exposure induces cardiac remodeling and aggravates high-fat diet-induced cardiac hypertrophy in mice - Beatriz Alexandre-Santos; Guilherme dos Santos Reis; Gabriela Rodrigues Medeiros; Milena Barcza Stockler-Pinto; Nathalia Silva Carlos Oliveira; Leandro Miranda-Alves; Antonio Claudio Lucas da Nóbrega; D'Angelo Carlo Magliano; Eliete Dalla Corte Frantz (Environmental Research, 2024)

Impact of sperm sex sorting on sperm quality and in vitro embryo production in bovine - Ligiane de Oliveira Leme; José Oliveira Carvalho; Camilla Motta Mendes; Mayra Elena Ortiz D'Avila Assumpção; Alexandre Rodrigues Caetano; Maurício Machaim Franco; Margot Alves Nunes Dode (Animal Reproduction Science, 2024)

Hydrocarbon composition of oils spilt on the Brazilian coast in 2019 and 2022 - Antônia M. Corrêa; Felipe F. Campos; Marcus F. Tenório; Alice M.S. Rodrigues; Carlos D. Pérez; Fabiano Thompson; Andressa S. Batista; Pedro V. Gatts; Carlos E. de Rezende; Kátia Z. Leal; Marcelo C. Bernardes (Marine Pollution Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Pennsylvanian epicontinental sea dynamics in Western Gondwana: Stratigraphic, petrographic, and C, O, and Sr isotopic insights from the Itaituba Formation, Amazonas Basin - Maria D. Traslaviña-Bueno; Juliana C. Marques; Afonso C. Nogueira; Pedro A. Silva; Juan S. Gomez-Neita; Amanda G. Rodrigues; André A. Martins; Paulo A. Souza; Ana K. Scomazzon; Marcia E. Longhim (Journal of South American Earth Sciences, 2024)

Analysis of environmental variables and deforestation in the amazon using logistical regression models - Helder J. F. da Silva; Weber A. Gonçalves; Bergson G. Bezerra; Cláudio M. Santos e Silva; Cristiano P. de Oliveira; Jório B. Cabral Júnior; Daniele T. Rodrigues; Fabrício D. S. Silva (Environmental Monitoring and Assessment, 2024)

Sonification of electronic dynamical systems: Spectral characteristics and sound evaluation using EEG features - G. Acosta Martínez; E. Guevara; E. S. Kolosovas-Machuca; P. G. Rodrigues; D. C. Soriano; E. Tristán Hernández; L. J. Ontañón-García (Cognitive Neurodynamics, 2024)

Setting up a CFD model to evaluate the impact of green infrastructures on local air quality - V. Rodrigues; B. Augusto; K. Oliveira; A. Ascenso; S. Rafael; D. Nascimento; A. I. Miranda (Air Quality, Atmosphere & Health, 2024)
Green infrastructures have been pointed out as innovative solutions to deal with current and future challenges related to air pollution and climate change. Although the potential of green infrastructures, such as green walls and green roofs, to mitigate air pollution has been documented, evidence at a local scale is still limited. This work aims to increase knowledge about the potentialities of green infrastructures in improving local air quality, focusing on particulate matter, nitrogen dioxide and ozone pollutants, and by using a local-scale computational fluid dynamics model. The ENVI-met model was applied to a particular hour of a summer day over a built-up environment centred on a main avenue in the city of Lisbon (Portugal). The dimensions of the computational domain are 618 m × 594 m × 143 m, and it contains 184 buildings, with the tallest building being 56 m. In addition to the baseline simulation, modelling was also done considering the application of green walls and green roofs to specific buildings located near the main avenue, together with a green corridor. The overall results show no disturbances exerted by green walls on the turbulent flow dynamics and on the air quality levels when compared to the baseline scenario (without green walls). The integrated scenario, which includes green walls, green roofs and a green corridor, will lead to potential local benefits of green infrastructures on O 3 concentrations, followed by variable impacts on NO 2 and particulate matter concentrations.

Revolutionizing food safety with electrochemical biosensors for rapid and portable pathogen detection - Brígida D’ Ávila Oliveira; Raíssa Soares Gomes; Alice Mendes de Carvalho; Emília Maria França Lima; Uelinton Manoel Pinto; Luciana Rodrigues da Cunha (Brazilian Journal of Microbiology, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Resistance training improves cardiac function in older women: a randomized controlled trial - Ricardo J. Rodrigues; Paolo M. Cunha; João P. Nunes; Lauro C. Vianna; Patrícia C. Brum; Danilo S. Bocalini; Andrei C. Sposito; Luis C. Miguita Junior; Max D. Oliveira; Elaine Batistella; Rodrigo R. Fernandes; Paulo S. Junior; et al. (GeroScience, 2024)

Assessing interpreter’s disagreements in land cover reference data collection from historical Landsat time series in Amazon - Mariane S. Reis; Lucélia S. de Barros; Manoel R. Rodrigues Neto; Dayane Rafaela V. de Moraes; Noeli Aline P. Moreira; Gabriel Mikael R. Alves; Bruno V. Adorno; Cassiano Gustavo Messias; Luciano V. Dutra; Camilo D. Rennó; Sidnei João S. Sant’Anna; Maria Isabel S. Escada (International Journal of Remote Sensing, 2024)

Understanding the Atlantic influence on climate and vegetation dynamics in western Iberia over the last 2000 years - Ricardo N. Santos; Teresa Rodrigues; Filipa Naughton; Enno Schefuß; Dulce Oliveira; João Moreno; Pedro M. Raposeiro; Graciela Gil-Romera; Alistair Morgan; Manel Leira; Sandra D. Gomes; S. Nemiah Ladd; et al. (Quaternary Science Reviews, 2024)

Tracing uplift and erosion in orogenic settings using quartz luminescence sensitivity: Insights from the Northern Andes uplift - Carlos Ortiz; Mauricio Parra; Fernanda C.G. Rodrigues; Thays D. Mineli; André O. Sawakuchi (Quaternary Geochronology, 2024)

Effects of post-exercise cold-water immersion on performance and perceptive outcomes of competitive adolescent swimmers - Natanael P. Batista; Flávia A. de Carvalho; Caio R. D. Rodrigues; Jéssica K. Micheletti; Aryane F. Machado; Carlos M. Pastre (European Journal of Applied Physiology, 2024)
Purpose To evaluate the effects of repeated use of cold-water immersion (CWI) during a training week on performance and perceptive outcomes in competitive adolescent swimmers. Methods This randomized-crossover study included 20 athletes, who received each intervention [CWI (14 ± 1 °C), thermoneutral water immersion (TWI) (27 ± 1 °C) as placebo, and passive recovery (PAS)] three times a week between the land-based resistance training and swim training. The interventions were performed in a randomized order with a 1-week wash-out period. We tested athletes before and after each intervention week regarding swim (100 m freestyle sprints) and functional performance (flexibility, upper and lower body power, and shoulder proprioception). We monitored athlete’s perceptions (well-being, heaviness, tiredness, discomfort and pain) during testing sessions using a 5-item questionnaire. Athlete preferences regarding the interventions were assessed at the end of the study. We used generalized linear mixed models and generalized estimating equations for continuous and categorical variables, respectively (intervention x time). Results We found a time effect for swim performance ( p = .01) in which, regardless the intervention, all athletes improved sprint time at post-intervention compared to baseline. There was an intervention effect for pain ( p = .04) and tiredness ( p = .04), but with no significant post-hoc comparisons. We found no significant effects for other outcomes. All athletes reported a preference for CWI or TWI in relation to PAS. Conclusion The repeated use of CWI throughout a training week did not impact functional or swim performance outcomes of competitive adolescent swimmers. Perceptive outcomes were also similar across interventions; however, athletes indicated a preference for both CWI and TWI.

Stemphylium lycopersici immobilized in mesoporous of type MCM 48 as biocatalyst for ω-transamination reactions - Maria Sandra Ramos Queiroz; Glaciela Cristina Rodrigues da Silva; Nádia Ligianara D. Nyari; Rodrigo O.M.A. de Souza; Rogério Marcos Dallago; Denise Oliveira Guimarães; Marcelo Luis Mignoni; Ivana Correa Ramos Leal (Sustainable Chemistry and Pharmacy, 2024)

Dynamic re-sedimentation of lacustrine carbonates in the Búzios Field, pre-salt section of Santos Basin, Brazil - Sabrina D. Altenhofen; Amanda G. Rodrigues; Leonardo Borghi; Luiz F. De Ros (Journal of South American Earth Sciences, 2024)

The role of health and wellbeing in shaping local park experiences during the COVID-19 pandemic - Lauren A. Ferguson; Michael D. Ferguson; Krista Rodrigues; Darrick Evensen; Alexander R. Caraynoff; Kimberly Persson; Josephine B. Porter; Stephen Eisenhaure (Journal of Outdoor Recreation and Tourism, 2024)

Structure and morphology of chars and activated carbons obtained from thermal treatment of coal and biomass origin materials, including their wastes: Results from the ICCP Microscopy of Carbon Materials Working Group - G. Predeanu; M. Wojtaszek-Kalaitzidi; I. Suárez Ruiz; M.N Bălănescu; A. Gómez Borrego; M.D. Ghiran; P.C. Hackley; S. Kalaitzidis; J. Kus; M. Mastalerz; M. Misz-Kennan; S. Pusz; et al. (International Journal of Coal Geology, 2024)

Microencapsulation of Annona muricata L. seed extract for the control of Plutella xylostella - José Pedro da Silva; Irinaldo D. Basílio Júnior; Fernanda Emanuelle Mendonça de Morais; Alice Maria Nascimento de Araújo; TicianoG.do Nascimento; Valdemir da Costa Silva; JohnnatanD.de Freitas; Lucas Alceu Rodrigues de Lima; Roseane Cristina Predes Trindade (Biocatalysis and Agricultural Biotechnology, 2024)

Operationalizing Intentionality in Primate Communication: Social and Ecological Considerations - Evelina D. Rodrigues; Marlen Fröhlich (International Journal of Primatology, 2024)
An intentional transfer of information is central to human communication. When comparing nonhuman primate communication systems to language, a critical challenge is to determine whether a signal is used in intentional, goal-oriented ways. As it is not possible to directly observe psychological states in any species, comparative researchers have inferred intentionality via behavioral markers derived from studies on prelinguistic human children. Recent efforts to increase consistency in nonhuman primate communication studies undervalue the effect of possible sources of bias: some behavioral markers are not generalizable across certain signal types (gestures, vocalizations, and facial expressions), contexts, settings, and species. Despite laudable attempts to operationalize first-order intentionality across signal types, a true “multimodal” approach requires integration across their sensory components (visual-silent, contact, audible), as a signal from a certain type can comprise more than one sensory component. Here we discuss how the study of intentional communication in nonlinguistic systems is hampered by issues of reliability, validity, consistency, and generalizability. We then highlight future research avenues that may help to understand the use of goal-oriented communication by opting, whenever possible, for reliable, valid, and consistent behavioral markers, but also taking into account sampling biases and integrating detailed observations of intraspecific communicative interactions.

Feeding ecology and behavior of mimetic juveniles of the Maracaibo leatherjack Oligoplites palometa (Perciformes: Carangidae) observed in an Amazonian tidal channel - Alexya Cunha de Queiroz; Breno Barros; Adria D. Procópio; Tatiane N. Medeiros Rodrigues (Hydrobiologia, 2024)

The cost of genetic diagnosis of suspected hereditary pediatric cataracts with whole-exome sequencing from a middle-income country perspective: a mixed costing analysis - Luiza M. Neves; Márcia Pinto; Olivia A. Zin; Daniela P. Cunha; Bruna N. S. Agonigi; Fabiana L. Motta; Leonardo H. F. Gomes; Dafne D. G. Horovitz; Daltro C. Almeida; Jocieli Malacarne; Leticia Guida; Andressa Braga; et al. (Journal of Community Genetics, 2024)
Up to 25% of pediatric cataract cases are inherited. There is sparse information in the literature regarding the cost of whole-exome sequencing (WES) for suspected hereditary pediatric cataracts. Molecular diagnosis of suspected hereditary pediatric cataracts is important for comprehensive genetic counseling. We performed a partial economic evaluation with a mixed costing analysis, using reimbursement data and microcosting approach with a bottom-up technique to estimate the cost of using WES for genetic diagnosis of suspected hereditary pediatric cataracts from the perspective of the Brazilian governmental health care system. One hundred and ten participants from twenty-nine families in Rio de Janeiro (RJ) were included. Costs of consumables, staff and equipment were calculated. Two scenarios were created: (1) The reference scenario included patients from RJ with suspected hereditary pediatric cataracts plus two family members. (2) The alternative scenario considered other genetic diseases, resulting in 5,280 exams per month. Sensitivity analysis was also performed. In the reference scenario, the total cost per exam was 700.09 United States dollars (USD), and in the alternative scenario, the total cost was 559.23 USD. The cost of WES alone was 527.85 USD in the reference scenario and 386.98 USD in the alternative scenario. Sensitivity analysis revealed that the largest costs were associated with consumables in both scenarios. Economic evaluations can help inform policy decisions, especially in middle-income countries such as Brazil.

Using dispersion models at microscale to assess long-term air pollution in urban hot spots: A FAIRMODE joint intercomparison exercise for a case study in Antwerp - F. Martín; S. Janssen; V. Rodrigues; J. Sousa; J.L. Santiago; E. Rivas; J. Stocker; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; et al. (Science of The Total Environment, 2024)

Origin and nature of pores in the Toolebuc Formation, a potential unconventional target in Australia - Xiaoxiao Mao; Grant K.W. Dawson; Victor Rudolph; Sandra Rodrigues; Suzanne D. Golding (International Journal of Coal Geology, 2024)

Evaluation of different ratios of neutral detergent-soluble carbohydrate fractions on performance, ingestive behavior, and nitrogen balance in dairy goats - Marco A. D. Bomfim; MarceloT. Rodrigues; Tadeu S. Oliveira (Tropical Animal Health and Production, 2024)

Responses of soil microbiome to copper-based materials (nano and bulk) for agricultural applications: An indoor-mesocosm experiment - Sara Peixoto; Rui G. Morgado; Marija Prodana; Diogo N. Cardoso; Catarina Malheiro; Joana Neves; Cátia Santos; Zahra Khodaparast; Maria D. Pavlaki; Sandra Rodrigues; Sónia M. Rodrigues; Isabel Henriques; et al. (NanoImpact, 2024)

Assessment of the profile of fungal defense-related metabolites in tomatoes during ripening by classical and NMR techniques - Marcy Heli Paiva Rodrigues; Roseane Farias d’Avila; Diego da Costa Cabrera; Eliana Badiale Furlong (Food Bioscience, 2024)

Application of ozone at low-pressure: Control of egg and larval phases of Zabrotes subfasciatus, inactivation of Aspergillus flavus and qualitative changes in bean grains - Eugénio da Piedade Edmundo Sitoe; Ernandes Rodrigues de Alencar; Lêda Rita D'Antonino Faroni; Edimar Aparecida Filomeno Fontes; Marcus Vinicius de Assis Silva; Franklin Jackson Machado; Ravi Pandiselvam; Carollayne Gonçalves Magalhães (Food Control, 2024)

An acute bout of resistance exercise increases BDNF in hippocampus and restores the long-term memory of insulin-resistant rats - Camila Berbert-Gomes; Júlia S. Ramos; João G. Silveira-Rodrigues; Daniel M. M. Leite; Bruno P. Melo; Danusa D. Soares (Experimental Brain Research, 2024)

Unravelling the fate of foliar-applied nickel in soybean: a comprehensive investigation - Jessica Bezerra de Oliveira; Jose Lavres; Peter M. Kopittke; Rufus L. Chaney; Hugh H. Harris; Peter D. Erskine; Daryl L. Howard; André Rodrigues dos Reis; Antony van der Ent (Plant and Soil, 2024)
Background and aims Nickel (Ni) deficiency has been reported to occur in soybean ( Glycine max ) grown on leached tropical soils in Brazil. We aimed to determine whether an internal or external Ni supply can compensate for low Ni within the seed by assessing whether the amount of Ni in the seed whether the foliar-application of aqueous NiSO 4 influenced the uptake of Ni by the leaf, the nutritional status of the plant, urease activity and growth. Methods We used Ni-depleted seeds (<0.35 μg Ni per g) and Ni-sufficient seeds (11.1 μg Ni g −1 ) for hydroponic experiments. Seedlings were grown either with or without an external Ni supply (0 or 0.85 μM Ni in nutrient solution) and either with or without an internal Ni supply (with or cotyledons removed). In addition, we used synchrotron-based micro-X-ray fluorescence analysis to examine the distribution of foliar-applied Ni (50 and 100 mg L -1 ). Key results Leaf Ni concentration and urease activity were both enhanced by increasing either the internal (cotyledon seed store) or external (solution) Ni supply. In addition, plants derived from Ni-depleted seed that received external Ni supply had 9.2% higher biomass relative to plants derived from Ni-sufficient seeds which received Ni. When foliar-applied, Ni accumulated in the pedicles of the trichomes within 15 minutes of application, and then moved to the vascular bundles before dispersing further into tissues within 3 hours. Conclusions Trichomes are an important pathway for foliar Ni absorption in soybean, but there are still major knowledge gaps our understanding of the physiological function of trichomes in the uptake of metal ions from foliar micro-nutrient treatments.

Performance of spray nozzles and droplet size on glufosinate deposition and weed biological efficacy - Evandro P. Prado; Júlio C. Guerreiro; Pedro J. Ferreira-Filho; Vagner do Nascimento; Samuel Ferrari; Fernando S. Galindo; Marina Funichello; Carlos G. Raetano; Paulo H. Pagliari; Rodolfo G. Chechetto; Arthur D. Rodrigues Neto (Crop Protection, 2024)

Use of remote sensing for linkage mapping and genomic prediction for common rust resistance in maize - Alexander Loladze; Francelino A. Rodrigues; Cesar D. Petroli; Carlos Muñoz-Zavala; Sergio Naranjo; Felix San Vicente; Bruno Gerard; Osval A. Montesinos-Lopez; Jose Crossa; Johannes W.R. Martini (Field Crops Research, 2024)

Glyphosate hormesis effects on the vegetative and reproductive development of glyphosate-susceptible and -resistant Conyza sumatrensis biotypes - Victor José Salomão Cesco; Fábio Henrique Krenchinski; Danilo Morilha Rodrigues; Ricardo Alcántara-de la Cruz; Stephen O. Duke; Edivaldo D. Velini; Caio A. Carbonari (Environmental Pollution, 2024)

Association between low-temperature drying and ozonation processes to control pests and preserve maize quality - Sampson Uzoma; Ernandes Rodrigues de Alencar; Lêda Rita D'Antonino Faroni; Marcus Vinicius de Assis Silva; Eugénio da Piedade Edmundo Sitoe; Ravi Pandiselvam; Solimar Gonçalves Machado (Food Control, 2024)

Effects of Acacia mearnsii tannins on growth performance, footpad dermatitis, nutrient digestibility, intestinal permeability, and meat quality of broiler chickens - Guilherme L. Godoy; Beatriz N. Rodrigues; Jessica C. Agilar; Valeria Biselo; Danielle D. Brutti; Greicy S. Maysonnave; Catarina Stefanello (Animal Feed Science and Technology, 2024)

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

Fungal Cultivars of Higher Attine Ants Promote Escovopsis Chemotropism - Karina B. de Oliveira; Aryel C. Goes; Airton D. Silva; Paulo C. Vieira; Andre Rodrigues (Current Microbiology, 2024)

Effects of feeding mycotoxin-contaminated diets and the use of an adsorbent on the intake, digestibility, rumen fermentation, nitrogen balance and physiological parameters in the blood of Nellore steers - Luis Henrique C. Batista; Gustavo R. Siqueira; Luiz F. Costa e Silva; Anne Koontz; Yury T. Granja-Salcedo; Igor M. Ferreira; Iorrano A. Cidrini; Karla A. Oliveira; Amanda Caroliny M. de Queiroz; Aline N. Rodrigues; Flávio D. de Resende (Animal Feed Science and Technology, 2024)

Solar photocatalysis using post-consumer alkaline batteries for degrading contaminants of emerging concern in surface water - Guenther Carlos C. Viana; Elisângela Maria R. Rocha; Elisandra Scapin; Arthur Cahino; Iris Rebeca D. Leite; Daniel A. Bertuol; José D. Ardisson; Daniel Aparecido S. Rodrigues; Camila C. Amorim (Journal of Environmental Chemical Engineering, 2023)

Ozonation for Pseudomonas paracarnis control: biofilm removal and preservation of chicken meat during refrigerated storage - Ejima Akogwu Okolo; Ernandes Rodrigues de Alencar; Solimar Goncalves Machado; Lêda Rita D’Antonino Faroni; Marcus Vinicius de Assis Silva; Nayara Aparecida da Silva Costa; Andressa Falqueto (Brazilian Journal of Microbiology, 2023)

Genetic diversity of adenovirus in neotropical bats from Brazil - Laís Santos Rizotto; Larissa Mayumi Bueno; Thaís Camilo Corrêa; Maria Vitória dos Santos de Moraes; Amanda de Oliveira Viana; Laura Morais Nascimento Silva; Julia Cristina Benassi; Guilherme Pereira Scagion; Bruna Larotonda Telezynski Lopes; Isabela Barbosa de Assis; Tatiana Ometto; Erick Gustavo Dorlass; et al. (Brazilian Journal of Microbiology, 2023)

A tribute to a man of science: lessons from Professor Luiz R. Travassos (1938–2020) - Marcio L. Rodrigues; Joshua D. Nosanchuk; Leonardo Nimrichter; Rosana Puccia (Brazilian Journal of Microbiology, 2023)

Definition of protocols for cryopreservation and three-dimensional in vitro culture of prepubertal goat testicular tissue after histomorphological, ultrastructural, and functional analysis - F.D.R. Gomes; L.V.S. Ñaupas; G.J.Q. Palomino; R.H.Y Celiz; N.A.R. Sá; M.A.S. Novaes; A.C.A. Ferreira; D.C.C. Brito; V.J.F. Freitas; B.N. Costa; C.M. Lucci; C.C.L. Fernandes; et al. (Theriogenology, 2023)

Tissue composition and storage duration affect the usefulness of generic wet-to-dry mass conversion factors in toxicology studies - Chloé Warret Rodrigues; Debbie Armstrong; Feiyue Wang; James D. Roth (Environmental Research, 2023)

Long-term memory in Staphylococcus aureus α-hemolysin ion channel kinetics - M. P. Silva; C. G. Rodrigues; D. C. Machado; R. A. Nogueira (European Biophysics Journal, 2023)

Drifting in the deep: Metatranscriptomics and metabarcoding reveal sustained metabolic activity and community composition in hydrothermal vent plume microbial communities - Jennifer M. Polinski; Mattie Rodrigue; Jason D. Meyer; Matthew J. Harke (Frontiers in Marine Science, 2023)
The deep sea is the largest habitat on our planet, supporting a vast diversity of organisms which have yet to be fully described. This habitat is punctuated by hydrothermal vents in which energy derived from chemosynthesis drives carbon fixation, supporting a complex and rich food web. Connectivity between vent systems remains an active area of research, with questions as to how vent-influenced microbial function and diversity persists over space and time. In particular, the role hydrothermal vent plumes play as potential highways for connectivity and biogeography is not well understood. To add to the growing body of research, this study sampled plume waters above the Moytirra hydrothermal vent field, located just north of the Azores. We examined how hydrothermal vent plume community biodiversity and metabolic activities change with distance from the vent using a combination of metabarcoding and metatranscriptomic sequencing. We detected a rich diversity of both prokaryotic and eukaryotic organisms inhabiting the plume, which remained metabolically active for kilometers from the vent source. Enriched sulfur metabolism functional signals and relative abundance of sulfur oxidizing bacteria suggest reduced sulfur compounds are a fundamental energy source within plume waters. Additionally, we observed evidence of top-down controls on primary production through both known grazers and putative viral activity. Although community-level functional signals suggest active metabolic functions for over a kilometer north or south of the vent field, these functions grew increasingly dissimilar to those observed directly above the vent site, and bacterial communities displayed indications of entering quiescent stages, likely due to decreasing resources and reduced temperatures. These data provide a first glimpse of Moytirra’s microbial biodiversity, in addition to providing a high-resolution understanding of life on the drift within a hydrothermal plume, its persistence with distance, and implications for connectivity.

Effect of the combined use of monensin with virginiamycin or bacitracin on beef cattle performance, liver gluconeogenesis, lipid metabolism and intramuscular fat content - José M. Oliveira Júnior; Bruno G.C. Homem; Daniel Cunha; Ítalo B.G. Lima; Aline C. Rodrigues; Felipe C. Maciel; Edmilson H.R. Domingues; German D. Ramírez-Zamudio; Priscilla D. Teixeira; Tathyane R.S. Gionbelli; Matheus H. Moretti; Daniel R. Casagrande; et al. (Animal Feed Science and Technology, 2023)

Plastisphere composition in a subtropical estuary: Influence of season, incubation time and polymer type on plastic biofouling - Tobias Sérvulo; Joe D. Taylor; Maíra C. Proietti; Lucas d.S. Rodrigues; Igor P. Puertas; Roberta A. Barutot; Ana L.d.F. Lacerda (Environmental Pollution, 2023)

Behavior of deteriogenic fungi in aviation fuels (fossil and biofuel) during simulated storage - Mariane Rodrigues Lobato; Juciana Clarice Cazarolli; Regiane Débora Fernandes Rios; Emmanuel Bezerra D’ Alessandro; Marcia T. S Lutterbach; Nelson Roberto Antoniosi Filho; Vânya Márcia Duarte Pasa; Donato Aranda; Pedro Rodrigo Scorza; Fátima Menezes Bento (Brazilian Journal of Microbiology, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

Transforming iron ore processing – Simplifying the comminution and replacing reverse flotation with magnetic and gravity separation - Armando F. d. V. Rodrigues; Homero Delboni; Klaydison Silva; James Zhou; Kevin P. Galvin; Lev O. Filippov (Minerals Engineering, 2023)

New insights into the Cretaceous evolution of the Western Amazonian paleodrainage system - Mariana de Assunção Rodrigues; Martin Roddaz; Roberto Ventura Santos; Melanie Louterbach; Carlos D'Apolito; Stéphane Brusset; Elton Luiz Dantas; Francisco Ricardo Negri (Sedimentary Geology, 2023)

Heated environment offsets the cardiovascular responses to prolonged rowing exercise in competitive athletes - Igor V.P. dos S. Barreto; Gabriel D. Rodrigues; Josie de S. Oliveira; Eduardo B. Neves; Pedro Paulo da S. Soares (Journal of Thermal Biology, 2023)

Removal of Reactive Dyes from a Real Bichromatic Textile Effluent Employing Bio-Based Nanomagnetic Adsorbents - Kátia C. H. Bezerra; Jacqueline R. Nascimento; Tiago D. Martins; Sherlan G. Lemos; Elma N. V. M. Carrilho; Christiane de A. Rodrigues; Geórgia Labuto (Water, Air, & Soil Pollution, 2023)

An exonuclease V homologue is expressed predominantly during early megasporogenesis in apomictic Brachiaria brizantha - Diva M. A. Dusi; Elizângela R. Alves; Gláucia B. Cabral; Luciane V. Mello; Daniel J. Rigden; Érica D. Silveira; Márcio Alves-Ferreira; Larissa A. Guimarães; Ana Cristina M. M. Gomes; Júlio C. M. Rodrigues; Vera T. C. Carneiro (Planta, 2023)

Combined Application of Antisense Oligomers to Control Transcription Factors of Candida albicans Biofilm Formation - D. Araújo; B. Gonçalves; D. Vilas Boas; M. E. Rodrigues; M. Henriques; S. Silva (Mycopathologia, 2023)

Environmental sensitivity index maps to manage oil spill risks: A review and perspectives - Fernando Mazo D'Affonseca; Fábio Augusto Gomes Vieira Reis; Claudia Vanessa dos Santos Corrêa; Arthur Wieczorek; Lucilia do Carmo Giordano; Mara Lúcia Marques; Flávio Henrique Rodrigues; Daiana Marques Costa; André de Andrade Kolya; Vinicius Mendes Veiga; Sarah Félix Santos; Laila Milani Magalhães; et al. (Ocean & Coastal Management, 2023)

Estimation of soluble solids content and fruit temperature in 'Rocha' pear using Vis-NIR spectroscopy and the SpectraNet–32 deep learning architecture - J.A. Martins; D. Rodrigues; A.M. Cavaco; M.D. Antunes; R. Guerra (Postharvest Biology and Technology, 2023)

Monitoring the impacts of a mega-dam on Amazonian understorey herbs - Marcelo B. Medeiros; Washington L. Oliveira; Flávio R.O. Rodrigues; Renata D. Silva; Íris J.K. Ferreira; Wellyngton E. Ayala; Suelma R. Silva; Rafaela T. Souza; Marcelo F. Simon (Forest Ecology and Management, 2023)

Interaction between sulfur and selenium in agronomic biofortification of cowpea plants under field conditions - Vinícius Martins Silva; Lolita Wilson; Scott D. Young; Martin R. Broadley; Philip J. White; André Rodrigues dos Reis (Plant and Soil, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Acute bouts of aerobic and resistance exercise similarly alter inhibitory control and response time while inversely modifying plasma BDNF concentrations in middle-aged and older adults with type 2 diabetes - João G. Silveira-Rodrigues; Bruno T. Campos; André T. de Lima; Pedro H. M. Ogando; Camila B. Gomes; Patrícia F. Gomes; Ivana M. S. Aleixo; Danusa D. Soares (Experimental Brain Research, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Different selection criteria may relax competition for denning sites between expanding red foxes (Vulpes vulpes) and endemic Arctic foxes (Vulpes lagopus) on the low-Arctic tundra - Audrey Moizan; Chloe Warret Rodrigues; James D. Roth (Polar Biology, 2023)

Increased ATP Release and Higher Impact of Adenosine A2A Receptors on Corticostriatal Plasticity in a Rat Model of Presymptomatic Parkinson’s Disease - Francisco Q. Gonçalves; Filipe C. Matheus; Henrique B. Silva; Joana I. Real; Daniel Rial; Ricardo J. Rodrigues; Jean-Pierre Oses; António C. Silva; Nélio Gonçalves; Rui D. Prediger; Ângelo R. Tomé; Rodrigo A. Cunha (Molecular Neurobiology, 2023)
Extracellular ATP can be a danger signal, but its role in striatal circuits afflicted in Parkinson’s disease (PD) is unclear and was now investigated. ATP was particularly released at high stimulation intensities from purified striatal nerve terminals of mice, which were endowed with different ATP-P2 receptors (P2R), although P2R antagonists did not alter corticostriatal transmission or plasticity. Instead, ATP was extracellularly catabolized into adenosine through CD73 to activate adenosine A 2A receptors (A 2A R) modulating corticostriatal long-term potentiation (LTP) in mice. In the presymptomatic phase of a 6-hydroxydopamine rat model of PD, ATP release from striatal nerve terminals was increased and was responsible for a greater impact of CD73 and A 2A R on corticostriatal LTP. These observations identify increased ATP release and ATP-derived formation of extracellular adenosine bolstering A 2A R activation as a key pathway responsible for abnormal synaptic plasticity in circuits involved in the onset of PD motor symptoms. The translation of these findings to humans prompts extending the use of A 2A R antagonists from only co-adjuvants of motor control in Parkinsonian patients to neuroprotective drugs delaying the onset of motor symptoms.

Pre-assessments of plant conservation status in islands: the case of French Overseas Territories - S. Véron; A. Bernard; E. Lebreton; C. Rodrigues-Vaz; M. Durand; L. Procopio; M. Hélion; M. Gayot; G. Viscardi; G. A. Krupnick; C. M. S. Carrington; V. Boullet; et al. (Biodiversity and Conservation, 2023)

Eucalyptus botryoides ’ resin and its new 2- O -galloyl-1,6- O -di- trans - p -coumaroyl- β -D-glycopyranoside compound display good antimicrobial activity - Marcela Sayegh Serafim; Débora Munhoz Rodrigues; Victor Pena Ribeiro; Gari Vidal Ccana-Ccapatinta; Milton Groppo; Carlos Henrique Gomes Martins; Sérgio Ricardo Ambrósio; A. N. D. Jairo Kenupp Bastos (Natural Product Research, 2023)

Quartz OSL sensitivity from dating data for provenance analysis of pleistocene and holocene fluvial sediments from lowland Amazonia - Priscila E. Souza; Fabiano N. Pupim; Carlos E.M. Mazoca; Ian del Río; Thays D. Mineli; Fernanda C.G. Rodrigues; Naomi Porat; Gelvam A. Hartmann; André O. Sawakuchi (Quaternary Geochronology, 2023)

Clinical and Parasitological Evaluation of Ivermectin and Ivermectin + Pyrantel Against Oxyuris Equi in Equines - Vinícius D. Rodrigues; Mariana G. de Freitas; Bruno Milan; Guilherme H. Reckziegel; Dyego G.L. Borges; Matheus T.M. Nakatani; Juliane F. Tutija; Fernando de A. Borges (Journal of Equine Veterinary Science, 2023)

Methyl benzoate and nerolidol attract the cyclocephaline beetle Cyclocephala paraguayensis to trumpet flowers - Arodí P. Favaris; Amanda C. Túler; Weliton D. Silva; Marvin Pec; Sérgio R. Rodrigues; Artur C. D. Maia; José Maurício S. Bento (The Science of Nature, 2023)

Reservoir lithofacies study of the Toolebuc Formation, Eromanga Basin, Australia as a potential unconventional target - Xiaoxiao Mao; Sandra Rodrigues; Joan S. Esterle; Suzanne D. Golding (International Journal of Coal Geology, 2023)

Kraft lignin-based carbon xerogel/zinc oxide composite for 4-chlorophenol solar-light photocatalytic degradation: effect of pH, salinity, and simultaneous Cr(VI) reduction - Nicolas Perciani de Moraes; Abner de Siervo; Taynara Oliveira Silva; Robson da Silva Rocha; D. Amaranatha Reddy; Yu Lianqing; Marcos Roberto de Vasconcelos Lanza; Liana Alvares Rodrigues (Environmental Science and Pollution Research, 2023)

Occurrence and distribution of per-and polyfluoroalkyl substances (PFAS) in surface and groundwaters in an urbanized and agricultural area, Southern Brazil - Paulo Henrique Prado Stefano; Ari Roisenberg; Raphael D’Anna Acayaba; Aline Pereira Roque; Daniela Rodrigues Bandoria; Aluisio Soares; Cassiana Carolina Montagner (Environmental Science and Pollution Research, 2023)

Mouse organoids as an in vitro tool to study the in vivo intestinal response to cytotoxicants - F. Jardi; C. Kelly; C. Teague; H. Fowler-Williams; D. C. Sevin; D. Rodrigues; H. Jo; S. Ferreira; B. Herpers; M. Van Heerden; T. de Kok; C. Pin; et al. (Archives of Toxicology, 2023)

Oral Medicine Experience and Attitudes Toward Oral Cancer: An Evaluation of Dentists Working in Primary Health Care - Jéssica Rodriguez Strey; Michelle Roxo-Gonçalves; Bianca Dutra Guzenski; Marco Antonio Trevizani Martins; Juliana Romanini; Maria Antonia Zancanaro de Figueiredo; Otávio Pereira D’Ávila; Marcelo Rodrigues Gonçalves; Roberto Nunes Umpierre; Erno Harzheim; Laura de Campos Hildebrand; Vinicius Coelho Carrard (Journal of Cancer Education, 2022)

Diagnosing similarities in probabilistic multi-model ensembles: an application to soil–plant-growth-modeling - Aline Schäfer Rodrigues Silva; Tobias K. D. Weber; Sebastian Gayler; Anneli Guthke; Marvin Höge; Wolfgang Nowak; Thilo Streck (Modeling Earth Systems and Environment, 2022)
There has been an increasing interest in using multi-model ensembles over the past decade. While it has been shown that ensembles often outperform individual models, there is still a lack of methods that guide the choice of the ensemble members. Previous studies found that model similarity is crucial for this choice. Therefore, we introduce a method that quantifies similarities between models based on so-called energy statistics. This method can also be used to assess the goodness-of-fit to noisy or deterministic measurements. To guide the interpretation of the results, we combine different visualization techniques, which reveal different insights and thereby support the model development. We demonstrate the proposed workflow on a case study of soil–plant-growth modeling, comparing three models from the Expert-N library. Results show that model similarity and goodness-of-fit vary depending on the quantity of interest. This confirms previous studies that found that “there is no single best model” and hence, combining several models into an ensemble can yield more robust results.

Determination of the internal dose due to the intake of 226Ra and 210Pb in drinking water from deep wells in the Metropolitan Region of Recife−Brazil - Romilton dos Santos Amaral; Niége Maria de Paiva Melo; José Araújo dos Santos Júnior; Arykerne Nascimento Casado da Silva; Filipe Lopes B. Correia; Zahily Herrero Fernández; Luís Rodrigo D.´Andrada Bezerra; Alberto Antônio da Silva; Andrey José Isidoro de Araújo Rodrigues Azevedo (Environmental Monitoring and Assessment, 2022)

Therapeutic hypothermia for the treatment of neonatal hypoxia-ischemia: sex-dependent modulation of reactive astrogliosis - Rafael Bandeira Fabres; Ricardo Ribeiro Nunes; Marcel de Medeiros de Mattos; Mirella Kielek Galvan Andrade; Ana Paula Rodrigues Martini; Isadora D’Ávila Tassinari; Eduardo Farias Sanches; Luciano Stürmer de Fraga; Carlos Alexandre Netto (Metabolic Brain Disease, 2022)

Exploring greetings and leave-takings: communication during arrivals and departures by chimpanzees of the Bossou community, Guinea - Evelina D. Rodrigues; António J. Santos; Misato Hayashi; Tetsuro Matsuzawa; Catherine Hobaiter (Primates, 2022)

An update on the phylogeny of Spintharinae with analysis based on morphological characters and taxonomy of Janula (Araneae, Theridiidae) - Everton Nei Lopes Rodrigues; Patrícia E. S. Rodrigues; Antonio D. Brescovit; Joseph K. H. Koh (Organisms Diversity & Evolution, 2022)

Are the current commercially available oximes capable of reactivating acetylcholinesterase inhibited by the nerve agents of the A-series? - Marcelo C. Santos; Fernanda D. Botelho; Arlan S. Gonçalves; Daniel A. S. Kitagawa; Caio V. N. Borges; Taynara Carvalho-Silva; Leandro B. Bernardo; Cíntia N. Ferreira; Rafael B. Rodrigues; Denise C. Ferreira Neto; Eugenie Nepovimova; Kamil Kuča; et al. (Archives of Toxicology, 2022)

Feeding behavior of post-weaned crossbred steers supplemented in the dry season of the year - Túlio Otávio Jardim D.’Almeida Lins; Robério Rodrigues Silva; Fabrício Bacelar Lima Mendes; Fabiano Ferreira da Silva; Everton Santos Bastos; Tarcísio Ribeiro Paixão; João Wilian Dias Silva; Marceliana da Conceição Santos; Gabriel Chaves Figueiredo; Henry Daniel Ruiz Alba; Gleidson Giordano Pinto de Carvalho (Tropical Animal Health and Production, 2022)

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

Asynchrony, density dependence, and persistence in an amphibian - Freya E. Rowland; Elizabeth S. Schyling; L. Kealoha Freidenburg; Mark C. Urban; Jonathan L. Richardson; A. Z. Andis Arietta; Susan B. Rodrigues; Adriana D. Rubinstein; Michael F. Benard; David K. Skelly (Ecology, 2022)
Understanding drivers of metapopulation dynamics remains a critical challenge for ecology and conservation. In particular, the degree of synchrony in metapopulation dynamics determines how resilient a metapopulation is to a widespread disturbance. In this study, we used 21 years of egg mass count data across 64 nonpermanent freshwater ponds in Connecticut, USA to evaluate patterns of abundance and growth and to assess regional as well as local factors in shaping the population dynamics of wood frogs ( Rana sylvatica = Lithobates sylvaticus ). In particular, we asked whether a species known to undergo metapopulation dynamics exhibited spatial synchrony in abundances. With the exception of a single year when breeding took place during severe drought conditions, our analyses revealed no evidence of synchrony despite close proximity (mean minimum distance

Multiresistant bacteria isolated from domestic and wild animals with skin lesions were susceptible to native plants from Southern Brazil - Claudia Giordani; Stefanie Bressan Waller; Karina Affeldt Guterres; Cristine Cioato da Silva; Raulene Rodrigues Lobo; Jéssica Fernanda Hoffmann; Soliane Carra Perera; Fábio Clasen Chaves; Sílvia Regina Leal Ladeira; Eliza Simone Viegas Sallis; Gilberto D’Ávila Vargas; Marlete Brum Cleff (Natural Product Research, 2022)

Involvement of serotonergic neurotransmission in the antidepressant-like effect elicited by cholecalciferol in the chronic unpredictable stress model in mice - Vivian B. Neis; Isabel Werle; Morgana Moretti; Priscila B. Rosa; Anderson Camargo; Yasmim de O. Dalsenter; Nicolle Platt; Axel F. Rosado; William D. Engel; Gudrian Ricardo L. de Almeida; Ingrid Selhorst; Alcir Luiz Dafre; et al. (Metabolic Brain Disease, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

NeoBat Interactions: A data set of bat–plant interactions in the Neotropics - Guillermo L. Florez‐Montero; Renata L. Muylaert; Marcelo R. Nogueira; Cullen Geiselman; Sharlene E. Santana; Richard D. Stevens; Marco Tschapka; Francisco A. Rodrigues; Marco A. R. Mello (Ecology, 2022)
Data papers and open databases have revolutionized contemporary science, as they provide the long‐needed incentive to collaborate in large international teams and make natural history information widely available. Nevertheless, most data papers have focused on species occurrence or abundance, whereas interactions have received much less attention. To help fill this gap, we have compiled a georeferenced data set of interactions between 93 bat species of the family Phyllostomidae (Chiroptera) and 501 plant species of 68 families. Data came from 169 studies published between 1957 and 2007 covering the entire Neotropical Region, with most records from Brazil (34.5% of all study sites), Costa Rica (16%), and Mexico (14%). Our data set includes 2571 records of frugivory (75.1% of all records) and nectarivory (24.9%). The best represented bat genera are Artibeus (28% of all records), Carollia (24%), Sturnira (10.1%), and Glossophaga (8.8%). Carollia perspicillata (187), Artibeus lituratus (125), Artibeus jamaicensis (94), Glossophaga soricina (86), and Artibeus planirostris (74) were the bat species with the broadest diets recorded based on the number of plant species. Among the plants, the best represented families were Moraceae (17%), Piperaceae (15.4%), Urticaceae (9.2%), and Solanaceae (9%). Plants of the genera Cecropia (46), Ficus (42), Piper (40), Solanum (31), and Vismia (27) exhibited the largest number of interactions. These data are stored as arrays (records, sites, and studies) organized by logical keys and rich metadata, which helped to compile the information on different ecological and geographic scales, according to how they should be used. Our data set on bat–plant interactions is by far the most extensive, both in geographic and taxonomic terms, and includes abiotic information of study sites, as well as ecological information of plants and bats. It has already facilitated several studies and we hope it will stimulate novel analyses and syntheses, in addition to pointing out important gaps in knowledge. Data are provided under the Creative Commons Attribution 4.0 International License. Please cite this paper when the data are used in any kind of publication related to research, outreach, and teaching activities.

Indigenous and local communities can boost seed supply in the UN decade on ecosystem restoration - Danilo Urzedo; Simone Pedrini; Daniel L. M. Vieira; Alexandre B. Sampaio; Bruna D. F. Souza; Eduardo Malta Campos-Filho; Fatima C. M. Piña-Rodrigues; Isabel B. Schmidt; Rodrigo G. P. Junqueira; Kingsley Dixon (Ambio, 2022)
The UN Decade of Ecosystem Restoration is poised to trigger the recovery of ecosystem services and transform structural injustices across the world in a way unparalleled in human history. The inclusion of diverse Indigenous and local communities to co-create robust native seed supply systems is the backbone to achieve the goals for the Decade. Here we show how community-based organizations have co-developed native seed supply strategies for landscape restoration from the bottom-up. We draw on the interconnections over two decades of seed networks in Brazil and the emerging Indigenous participation in native seed production in Australia. From an environmental justice perspective, we provide a participatory seed supply approach for local engagement, noting local geographical, social and cultural contexts. Meeting large-scale restoration goals requires the connection between local seed production and collaborative platforms to negotiate roles, rights and responsibilities between stakeholders. An enduring native seed supply must include a diversity of voices and autonomy of community groups that builds equitable participation in social, economic, and environmental benefits.

Molecular Detection of Trypanosoma kaiowa in Tabanus triangulum (Diptera: Tabanidae) from the Coastal Plain of Rio Grande do Sul, Southern Brazil - Gratchela D. Rodrigues; Eduardo Blodorn; Ândrio Zafalon-Silva; William Domingues; Roberta Marques; Tiago K. Krolow; Gonzalo Greif; Vinicius F. Campos; Rodrigo F. Krüger (Acta Parasitologica, 2022)

Reduced Cerebellar Brain Inhibition Measured Using Dual-Site TMS in Older Than in Younger Adults - B. K. Rurak; J. P. Rodrigues; B. D. Power; P. D. Drummond; A. M. Vallence (The Cerebellum, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Global distribution of material inflows to in‐use stocks in 2011 and its implications for a circularity transition - Glenn A. Aguilar‐Hernandez; Sebastiaan Deetman; Stefano Merciai; João F. D. Rodrigues; Arnold Tukker (Journal of Industrial Ecology, 2021)

Floating treatment wetland for nutrient removal and acute ecotoxicity improvement of untreated urban wastewater - L. H. Bauer; A. Arenzon; N. D. Molle; J. A. Rigotti; A. C. A. Borges; N. R. Machado; L. H. R. Rodrigues (International Journal of Environmental Science and Technology, 2021)

Vaccine Innovation for Pandemic Preparedness: Patent Landscape, Global Sustainability, and Circular Bioeconomy in Post-COVID-19 era - Cristina Possas; Adelaide Maria de Souza Antunes; Alessandra Moreira de Oliveira; Cristina d’Urso de Souza Mendes Santos; Mateus Pinheiro Ramos; Suzanne de Oliveira Rodrigues Schumacher; Akira Homma (Circular Economy and Sustainability, 2021)

Stability of tropical forest tree carbon‐water relations in a rainfall exclusion treatment through shifts in effective water uptake depth - Alexandria L. Pivovaroff; Nate G. McDowell; Tayana Barrozo Rodrigues; Tim Brodribb; Lucas A. Cernusak; Brendan Choat; Charlotte Grossiord; Yoko Ishida; Kolby J. Jardine; Susan Laurance; Riley Leff; Weibin Li; et al. (Global Change Biology, 2021)
Increasing severity and frequency of drought is predicted for large portions of the terrestrial biosphere, with major impacts already documented in wet tropical forests. Using a 4‐year rainfall exclusion experiment in the Daintree Rainforest in northeast Australia, we examined canopy tree responses to reduced precipitation and soil water availability by quantifying seasonal changes in plant hydraulic and carbon traits for 11 tree species between control and drought treatments. Even with reduced soil volumetric water content in the upper 1 m of soil in the drought treatment, we found no significant difference between treatments for predawn and midday leaf water potential, photosynthesis, stomatal conductance, foliar stable carbon isotope composition, leaf mass per area, turgor loss point, xylem vessel anatomy, or leaf and stem nonstructural carbohydrates. While empirical measurements of aboveground traits revealed homeostatic maintenance of plant water status and traits in response to reduced soil moisture, modeled belowground dynamics revealed that trees in the drought treatment shifted the depth from which water was acquired to deeper soil layers. These findings reveal that belowground acclimation of tree water uptake depth may buffer tropical rainforests from more severe droughts that may arise in future with climate change.

Dopaminergic Receptors as Neuroimmune Mediators in Experimental Autoimmune Encephalomyelitis - E. C. D. Gonçalves; V. Lieberknecht; V. V. Horewicz; B. D. Rabelo; F. A. Felipetti; A. L. S. Rodrigues; D. F. Martins; R. C. Dutra (Molecular Neurobiology, 2021)

Mismatch between bird species sensitivity and the protection of intact habitats across the Americas - Victor Cazalis; Megan D. Barnes; Alison Johnston; James E. M. Watson; Cagan H. Şekercioğlu; Ana S. L. Rodrigues (Ecology Letters, 2021)
Protected areas are highly heterogeneous in their effectiveness at buffering human pressure, which may hamper their ability to conserve species highly sensitive to human activities. Here, we use 60 million bird observations from eBird to estimate the sensitivity to human pressure of each bird species breeding in the Americas. Concerningly, we find that ecoregions hosting large proportions of high‐sensitivity species, concentrated in tropical biomes, do not have more intact protected habitat. Moreover, 266 high‐sensitivity species have little or no intact protected habitat within their distributions. Finally, we show that protected area intactness is decreasing faster where high‐sensitivity species concentrate. Our results highlight a major mismatch between species conservation needs and the coverage of intact protected habitats, which likely hampers the long‐term effectiveness of protected areas at retaining species. We highlight ecoregions where protection and management of intact habitats, complemented by restoration, is urgently needed.

Morphological and molecular discordance in the taxonomic rearrangement of the Marmosops pinheiroi complex (Marsupialia: Didelphidae) - Roger Rodrigues Guimarães; Rita Gomes Rocha; Ana Carolina Loss; Ana Cristina Mendes-Oliveira; Bruce D. Patterson; Leonora Pires Costa (Systematics and Biodiversity, 2021)

Effect of m-Trifluoromethyl-diphenyl diselenide on the Pain–Depression Dyad Induced by Reserpine: Insights on Oxidative Stress, Apoptotic, and Glucocorticoid Receptor Modulation - Cleisson Schossler Garcia; Pabliane Rodrigues Garcia; Carlos Natã da Silva Espíndola; Gustavo D’Avila Nunes; Natália Silva Jardim; Sabrina Grendene Müller; Cristiani Folharini Bortolatto; César Augusto Brüning (Molecular Neurobiology, 2021)

Global environmental and socio‐economic impacts of a transition to a circular economy in metal and electrical products: A Dutch case study - Bertram F. de Boer; Elmer Rietveld; João F. D. Rodrigues; Arnold Tukker (Journal of Industrial Ecology, 2021)

Toxicity Assays of Commercial Chlorpyrifos Under UV/H2O2 and UVC Photolysis Treatments - Suelen Angeli; Eliane Adams; Gabriella P. Masceno; Rúbia M. Lima; Larisa M. Utzig; Fernando Rodrigues-Silva; Liziê D. T. Prola; Adriane M. Freitas; Marcus V. Liz (Water, Air, & Soil Pollution, 2021)

Combining regional to local restoration goals in the Brazilian Atlantic forest - Cassia M.G. Lemos; Pedro R. Andrade; Ricardo R. Rodrigues; Leticia Hissa; Ana P. D. Aguiar (Regional Environmental Change, 2021)
To achieve regional and international large-scale restoration goals with minimum costs, several restoration commitments rely on natural regeneration, a passive and inexpensive strategy. However, natural regeneration potential may vary within the landscape, mainly due to its historical context. In this work, we use spatially explicit restoration scenarios to explore how and where, within a given region, multiple restoration commitments could be combined to achieve cost-effectiveness outcomes. Our goal is to facilitate the elaboration of forest restoration plans at the regional level, taking into consideration the costs for active and passive restoration methods. The approach includes (1) a statistical analysis to estimate the natural regeneration potential for a given area based on alternative sets of biophysical, land cover, and/or socioeconomic factors and (2) the use of a land change allocation model to explore the cost-effectiveness of combining multiple restoration commitments in a given area through alternative scenarios. We test our approach in a strategic region in the Brazilian Atlantic Forest Biome, the Paraiba Valley in São Paulo State. Using the available data for 2011, calibrated for 2015, we build alternative scenarios for allocating natural regeneration until 2025. Our models indicate that the natural regeneration potential of the region is actually very low, and the cost-effectiveness outcomes are similar for all scenarios. We believe our approach can be used to support the regional-level decision-making about the implementation of multiple commitments aiming at the same target area. It can also be combined with other approaches for more refined analysis (e.g., optimization models).

Identification of TIA1 mRNA targets during human neuronal development - Loryn P. Byres; Marat Mufteev; Kyoko E. Yuki; Wei Wei; Alina Piekna; Michael D. Wilson; Deivid C. Rodrigues; James Ellis (Molecular Biology Reports, 2021)
Background Neuronal development is a tightly controlled process involving multi-layered regulatory mechanisms. While transcriptional pathways regulating neurodevelopment are well characterized, post-transcriptional programs are still poorly understood. TIA1 is an RNA-binding protein that can regulate splicing, stability, or translation of target mRNAs, and has been shown to play critical roles in stress response and neurodevelopment. However, the identity of mRNAs regulated by TIA1 during neurodevelopment under unstressed conditions is still unknown. Methods and Results To identify the mRNAs targeted by TIA1 during the first stages of human neurodevelopment, we performed RNA immunoprecipitation-sequencing (RIP-seq) on human embryonic stem cells (hESCs) and derived neural progenitor cells (NPCs), and cortical neurons under unstressed conditions. While there was no change in TIA1 protein levels, the number of TIA1 targeted mRNAs decreased from pluripotent cells to neurons. We identified 2400, 845, and 330 TIA1 mRNA targets in hESCs, NPC, and neurons, respectively. The vast majority of mRNA targets in hESC were genes associated with neurodevelopment and included autism spectrum disorder-risk genes that were not bound in neurons. Additionally, we found that most TIA1 mRNA targets have reduced ribosomal engagement levels. Conclusion Our results reveal TIA1 mRNA targets in hESCs and during human neurodevelopment, indicate that translation repression is a key process targeted by TIA1 binding and implicate TIA1 function in neuronal differentiation.

Total and Organic Mercury in Fish from Different Geographical Areas in the North Atlantic Ocean and Health Risk Assessment - H. C. Vieira; M. M. B. Ramirez; M. D. Bordalo; A. C. M. Rodrigues; A. M. V. M. Soares; S. N. Abreu; F. Morgado; J. Rendón-von Osten (Exposure and Health, 2021)

Inter-laboratory automation of the in vitro micronucleus assay using imaging flow cytometry and deep learning - John W. Wills; Jatin R. Verma; Benjamin J. Rees; Danielle S. G. Harte; Qiellor Haxhiraj; Claire M. Barnes; Rachel Barnes; Matthew A. Rodrigues; Minh Doan; Andrew Filby; Rachel E. Hewitt; Catherine A. Thornton; et al. (Archives of Toxicology, 2021)
The in vitro micronucleus assay is a globally significant method for DNA damage quantification used for regulatory compound safety testing in addition to inter-individual monitoring of environmental, lifestyle and occupational factors. However, it relies on time-consuming and user-subjective manual scoring. Here we show that imaging flow cytometry and deep learning image classification represents a capable platform for automated, inter-laboratory operation. Images were captured for the cytokinesis-block micronucleus (CBMN) assay across three laboratories using methyl methanesulphonate (1.25–5.0 μg/mL) and/or carbendazim (0.8–1.6 μg/mL) exposures to TK6 cells. Human-scored image sets were assembled and used to train and test the classification abilities of the “DeepFlow” neural network in both intra- and inter-laboratory contexts. Harnessing image diversity across laboratories yielded a network able to score unseen data from an entirely new laboratory without any user configuration. Image classification accuracies of 98%, 95%, 82% and 85% were achieved for ‘mononucleates’, ‘binucleates’, ‘mononucleates with MN’ and ‘binucleates with MN’, respectively. Successful classifications of ‘trinucleates’ (90%) and ‘tetranucleates’ (88%) in addition to ‘other or unscorable’ phenotypes (96%) were also achieved. Attempts to classify extremely rare, tri- and tetranucleated cells with micronuclei into their own categories were less successful (≤ 57%). Benchmark dose analyses of human or automatically scored micronucleus frequency data yielded quantitation of the same equipotent concentration regardless of scoring method. We conclude that this automated approach offers significant potential to broaden the practical utility of the CBMN method across industry, research and clinical domains. We share our strategy using openly-accessible frameworks.

Textile effluent treatment employing yeast biomass and a new nanomagnetic biocomposite - Jacqueline R. Nascimento; Kátia C.H. Bezerra; Tiago D. Martins; Elma N.V.M. Carrilho; Christiane de A. Rodrigues; Geórgia Labuto (Environmental Science and Pollution Research, 2021)

Peptide fraction from latex of Calotropis procera exhibits antifungal and insecticidal activities - Jackson L. Amaral; Cleverson D. T. Freitas; João P. V. Rodrigues; Ghulam Hussain; Márcio V. Ramos; Pedro F. N. Souza (Arthropod-Plant Interactions, 2021)

Not just a methane source: Amazonian floodplain sediments harbour a high diversity of methanotrophs with different metabolic capabilities - Júlia B. Gontijo; Fabiana S. Paula; Andressa M. Venturini; Caio A. Yoshiura; Clovis D. Borges; José Mauro S. Moura; Brendan J.M. Bohannan; Klaus Nüsslein; Jorge L. Mazza Rodrigues; Siu M. Tsai (Molecular Ecology, 2021)
The Amazonian floodplain forests are dynamic ecosystems of great importance for the regional hydrological and biogeochemical cycles and function as a significant CH 4 source contributing to the global carbon balance. Unique geochemical factors may drive the microbial community composition and, consequently, affect CH 4 emissions across floodplain areas. Here, we report the in situ composition of CH 4 cycling microbial communities in Amazonian floodplain sediments. We considered how abiotic factors may affect the microbial community composition and, more specifically, CH 4 cycling groups. We collected sediment samples during wet and dry seasons from three different types of floodplain forests, along with upland forest soil samples, from the Eastern Amazon, Brazil. We used high‐resolution sequencing of archaeal and bacterial 16S rRNA genes combined with real‐time PCR to quantify Archaea and Bacteria, as well as key functional genes indicative of the presence of methanogenic ( mcr A) and methanotrophic ( pmo A) microorganisms. Methanogens were found to be present in high abundance in floodplain sediments, and they seem to resist the dramatic environmental changes between flooded and nonflooded conditions. Methanotrophs known to use different pathways to oxidise CH 4 were detected, including anaerobic archaeal and bacterial taxa, indicating that a wide metabolic diversity may be harboured in this highly variable environment. The floodplain environmental variability, which is affected by the river origin, drives not only the sediment chemistry but also the composition of the microbial communities. These environmental changes seem also to affect the pools of methanotrophs occupying distinct niches. Understanding these shifts in the methanotrophic communities could improve our comprehension of the CH 4 emissions in the region.

Environmental correlates of taxonomic and phylogenetic diversity in the Atlantic Forest - Andrea Paz; Jason L. Brown; Carlos L. O. Cordeiro; Julian Aguirre‐Santoro; Claydson Assis; Renata Cecilia Amaro; Fabio Raposo do Amaral; Thuane Bochorny; Lucas F. Bacci; Mayara K. Caddah; Fernando d’Horta; Miriam Kaehler; et al. (Journal of Biogeography, 2021)
Aim There is little consensus on which environmental variables are best at predicting multiple dimensions of diversity. We ask whether there are common environmental correlates of diversity, despite ecological differences, across nine clades of plants and animals distributed along a single rainforest domain. For that, we compare the environmental correlates of species richness, phylogenetic diversity, and phylogenetic endemism. Location Brazilian Atlantic Forest. Taxon: Five clades of plants (Bromelioideae, Miconieae, Bertolonia , Cambessedesieae, and the Fridericia and allies) and four clades of animals (butterlies in the tribe Ithomiini, frogs in the genera Boana and Proceratophrys , and birds in the subfamily Thraupinae). Methods Using curated occurrence localities and phylogenetic data, we generated maps of (a) species richness, (b) phylogenetic diversity, (c) residuals of phylogenetic diversity regressed on species richness, and (d) phylogenetic endemism for all groups. We also compiled a set of 30 environmental descriptors, including records of current temperature and precipitation, climatic stability over time, and topography. Through a machine learning framework, we explored the environmental correlates of each of these diversity measures for each group. Results The environmental variables used here were strong predictors of diversity for all studied groups. However, models for phylogenetic endemism had lower predictive power. Although patterns of diversity are different among groups, correlates of diversity are consistent across taxa. For both species richness and phylogenetic diversity, current precipitation and precipitation stability over time were consistently ranked among the variables that strongly correlate with diversity patterns. The correlates of phylogenetic endemism were less homogeneous across groups. The results suggest that including climate stability over time is important when predicting diversity measures that reflect historical components. Main conclusions Investigating environmental correlates of diversity for multiple clades and diversity measures in a single geographic area allows for a better understanding of common patterns across taxa. This study shows that environmental conditions, particularly precipitation, are good predictors of the patterns of species richness and phylogenetic diversity‐but not phylogenetic endemism‐across different Atlantic Forest groups.

Cottonseed meal with enzyme complex for finishing pigs - Jone Rodrigues da Silva; Rauana Vieira de Andrade; Anderson Corassa; Maicon Sbardella; Heder José D’Avila Lima; Vânia Maria Arantes; Alessandro Borges Amorim (Tropical Animal Health and Production, 2021)

Ketamine-induced urological toxicity: potential mechanisms and translation for adults with mood disorders receiving ketamine treatment - Jason Ng; Leanna M. W. Lui; Joshua D. Rosenblat; Kayla M. Teopiz; Orly Lipsitz; Danielle S. Cha; Jiaqi Xiong; Flora Nasri; Yena Lee; Kevin Kratiuk; Nelson B. Rodrigues; Hartej Gill; et al. (Psychopharmacology, 2021)

Scale‐dependent patterns of metacommunity structuring in aquatic organisms across floodplain systems - Fernando M. Lansac‐Tôha; Luis M. Bini; Jani Heino; Bianca R. Meira; Bianca T. Segovia; Carla S. Pavanelli; Claudia C. Bonecker; Claudia P. de Deus; Evanilde Benedito; Geziele M. Alves; Gislaine I. Manetta; Juliana D. Dias; et al. (Journal of Biogeography, 2021)
Aim Evaluating how groups of organisms vary in dispersal capability and how environmental, spatial and temporal signals vary across multiple scales is critical to elucidating metacommunity theory. We examined whether the relative contributions of environmental, spatial and hydrological factors have different effects on organismal groups with different dispersal abilities at three spatial scales, and how this knowledge contributes to our understanding of metacommunity dynamics. Location Four major Brazilian floodplains, with the largest distance among them of 2,300 Km. Taxon 10 aquatic organismal groups, ranging from bacterioplankton to fish. Methods We sampled lakes connected to the main river in the low‐ and high‐water periods of each floodplain between 2011 and 2012. Different biological groups were analysed across three hierarchical spatial scales (fine, intermediate and subcontinental) within and between floodplain systems. We applied a series of partial redundancy analyses to estimate the relative contributions of environmental factors, spatial factors and hydrological period for each biological group. Results At the fine spatial scale, predominantly environmental factors and hydrological period structure metacommunities, although less so for microorganisms than for micro‐invertebrates and macro‐organisms. The relative importance of environmental factors increased at the intermediate spatial scale. At the subcontinental scale, the relative importance of spatial factors increased for all biological groups, but environmental factors remained the primary regulators of microorganisms even at the largest scale. Main conclusions This study design allowed us to make more robust inferences about the mechanisms responsible for regulating community structure of distinct biological groups at different spatial scales. Our results suggest that biological groups displaying distinct body size likely determine the spatial extent at which environmental, spatial and hydrological processes prevail as the primary regulators of community structure. These findings are important in guiding the conservation and management of floodplain biodiversity because these systems are naturally highly heterogeneous in space and time.

Feeding behavior of feedlot-finished crossbred bulls fed palm kernel cake - Mateus de M. Lisboa; Robério R. Silva; Fabiano F. da Silva; Maria M. S. Pereira; Gabriel D. Costa; Fabrício B. L. Mendes; Sinvaldo O. de Souza; Marceliana da C. Santos; Laoan B. O. Rodrigues; Henry D. R. Alba; Gleidson G. P. de Carvalho (Tropical Animal Health and Production, 2021)

The usefulness of Olanzapine plasma concentrations in monitoring treatment efficacy and metabolic disturbances in first-episode psychosis - J. A. Arnaiz; C. Rodrigues-Silva; G. Mezquida; S. Amoretti; M. J. Cuesta; D. Fraguas; A. Lobo; A. González-Pinto; M. C. Díaz-Caneja; I. Corripio; E. Vieta; I. Baeza; et al. (Psychopharmacology, 2021)

The CORDEX Flagship Pilot Study in southeastern South America: a comparative study of statistical and dynamical downscaling models in simulating daily extreme precipitation events - M. L. Bettolli; S. A. Solman; R. P. da Rocha; M. Llopart; J. M. Gutierrez; J. Fernández; M. E. Olmo; A. Lavin-Gullon; S. C. Chou; D. Carneiro Rodrigues; E. Coppola; R. Balmaceda Huarte; et al. (Climate Dynamics, 2021)

Modeling the circular economy in environmentally extended input–output: A web application - Franco Donati; Sidney Niccolson; Arjan de Koning; Bart Daniels; Maarten Christis; Katrien Boonen; Theo Geerken; João F. D. Rodrigues; Arnold Tukker (Journal of Industrial Ecology, 2021)
Global environmental and resource problems ask for new ways of managing the production and consumption of resources. The implementation of new paradigms, such as the circular economy, requires decision‐makers at multiple levels to make complex decisions. For this, clear analyses and modeling of scenarios are of utmost importance. Meanwhile, as the sophistication of databases and models increases so does the need for user‐friendly tools to use them. The RaMa‐Scene web platform reduces these barriers by allowing users to visualize easily diverse impacts of implementing circular‐economy interventions. This online web platform makes use of the multi‐regional environmentally extended input–output database EXIOBASE version 3 in monetary units, which has been modified to show explicit transactions of raw materials from recycling activities.

Association between exposure to air pollution during intrauterine life and cephalic circumference of the newborn - Mariana Azevedo Carvalho; Karen Hettfleisch; Agatha S Rodrigues; Alexandra Benachi; Sandra Elisabete Vieira; Silvia R. D. M. Saldiva; Paulo Hilário N. Saldiva; Rossana Pulcineli Vieira Francisco; Lisandra Stein Bernardes (Environmental Science and Pollution Research, 2021)

Industrial wastewater treatment using a bubble photo-Fenton reactor with continuous gas supply - Emanuel F. S. Sampaio; Carmen S. D. Rodrigues; Vanessa N. Lima; Luis M. Madeira (Environmental Science and Pollution Research, 2021)

Marine Heatwaves, Sewage and Eutrophication Combine to Trigger Deoxygenation and Biodiversity Loss: A SW Atlantic Case Study - Kalina M. Brauko; Alex Cabral; Natasha V. Costa; Juliana Hayden; Carlos E. P. Dias; Edilene S. Leite; Renan D. Westphal; Carolina M. Mueller; Jason M. Hall-Spencer; Regina R. Rodrigues; Leonardo R. Rörig; Paulo R. Pagliosa; et al. (Frontiers in Marine Science, 2020)
Marine heatwaves (MHWs) are a major concern worldwide due to their increasing impacts in recent years, and these extreme events may trigger deoxygenation of coastal waters affected by sewage and eutrophication. Here we investigate the combined effects of MHWs and nutrient enrichment on the water quality and biodiversity of the Bay of Santa Catarina Island (Brazil). We used historical (1994–2020) sea surface temperature data from satellites and in situ physical, chemical and biological parameters to assess temporal trends. Oxygen levels have been decreasing whilst phosphorus levels have been increasing in the bay. During the austral summer of 2020 a regional sea surface heatwave was detected by satellite, lasting for 9 days and coinciding with our research cruise. During this period, seawater temperatures reached 29.8°C and anoxia was detected for the first time in the bay. A decrease in macrobenthic and phytoplankton community richness correlated with decreases in oxygen both through time and towards more urbanized areas. Overall, poor wastewater treatment is a key stressor that combined with MHWs to degrade coastal waters. Mitigation strategies are needed to minimize the impact of MHWs, including improved sewage treatment, restoration and conservation of wetlands and the use of nature-based technologies to promote coastal ecosystem recovery.

Recent advances on anaerobic digestion of swine wastewater - G. Lourinho; L. F. T. G. Rodrigues; P. S. D. Brito (International Journal of Environmental Science and Technology, 2020)

Intranasal administration of budesonide-loaded nanocapsule microagglomerates as an innovative strategy for asthma treatment - Manoel Ortiz; Diego de Sa Coutinho; Bianca Torres Ciambarella; Everton Tenorio de Souza; Ana Paula Leite D’Almeida; Taís Lusa Durli; Patrícia Machado Rodrigues e Silva; Andressa Bernardi; Fabio Sonvico; Adriana Raffin Pohlmann; Marco Aurelio Martins; Sílvia Stanisçuaski Guterres (Drug Delivery and Translational Research, 2020)

Characterization, antibacterial activity and antibiotic modifying action of the Caryocar coriaceum Wittm. pulp and almond fixed oil - Fladson F.G. Pereira; Maria K. S. B. Feitosa; Maria do S. Costa; Saulo R. Tintino; Fábio F.G. Rodrigues; Irwin R. A. Menezes; Henrique D. M. Coutinho; José G.M. da Costa; Erlânio O. de Sousa (Natural Product Research, 2020)

Ayahuasca blocks the reinstatement of methylphenidate-induced conditioned place preference in mice: behavioral and brain Fos expression evaluations - Henrique S. Reis; Isa R. S. Rodrigues; Alexia Anjos-Santos; Matheus Libarino-Santos; Yasmim A. Serra; Elisângela G. Cata-Preta; Daniella Oliveira-Campos; Natali D. Kisaki; Thaísa Barros-Santos; Thais S. Yokoyama; Fabio C. Cruz; Alexandre J. Oliveira-Lima; et al. (Psychopharmacology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Association between maternal exposure to air pollution before conception and sex determination in the city of São Paulo - Mariana Azevedo Carvalho; Karen Hettfleisch; Agatha S Rodrigues; Alexandra Benachi; Sandra Elisabete Vieira; Silvia R D M Saldiva; Paulo Hilário N. Saldiva; Rossana Pulcineli Vieira Francisco; Lisandra Stein Bernardes (Air Quality, Atmosphere & Health, 2020)

SERK genes identification and expression analysis during somatic embryogenesis and sporogenesis of sexual and apomictic Brachiaria brizantha (Syn. Urochloa brizantha) - Andréa D. Koehler; André S. T. Irsigler; Vera T. C. Carneiro; Glaucia B. Cabral; Júlio C. M. Rodrigues; Ana Cristina M. M. Gomes; Roberto C. Togawa; Marcos M. C. Costa; Adriana Pinheiro Martinelli; Diva Maria de Alencar Dusi (Planta, 2020)

Melaleuca leucadendra Essential Oil Promotes Loss of Cell Membrane and Wall Integrity and Inhibits Bacterial Growth: An In Silico and In Vitro Approach - Jessica P. Bautista-Silva; Janaína B. Seibert; Tatiane R. Amparo; Ivanildes V. Rodrigues; Luiz Fernando M. Teixeira; Gustavo Henrique B. Souza; Orlando D. H. dos Santos (Current Microbiology, 2020)

Mating system of Thrichomys fosteri in the Brazilian Pantanal: spatial patterns indicate promiscuity - Pâmela Antunes; Luiz Gustavo Rodrigues Oliveira-Santos; Thiago Mateus Rocha dos Santos; Jorge Fernando Saraiva de Menezes; Walfrido Moraes Tomas; James D. Forester; Fernando Antonio Santos Fernandez (Mammalian Biology, 2020)

P2X7 siRNA targeted to the kidneys increases klotho and delays the progression of experimental diabetic nephropathy - A. M. Rodrigues; R. S. Serralha; D. Y. Lima; G. R. Punaro; I. Visona; M. J. S. Fernandes; E. M. S. Higa (Purinergic Signalling, 2020)

Entomopathogenic Viruses in the Neotropics: Current Status and Recently Discovered Species - D R Sosa-Gómez; F S Morgado; R F T Corrêa; L A Silva; D M P Ardisson-Araújo; B M P Rodrigues; E E Oliveira; R W S Aguiar; B M Ribeiro (Neotropical Entomology, 2020)

Natural Enemies of the Harrisia Cactus Mealybug and Other Hypogeococcus Species (Hemiptera: Pseudococcidae) in Puerto Rico: Identification and Taxonomic Notes on Primary and Secondary Parasitoids - S. V. Triapitsyn; S. D. Hight; G. A. Logarzo; M. B. Aguirre; J. C. Verle Rodrigues; V. A. Trjapitzin; Z. Rivera Ocasio; M. L. Rivera-Vázquez; M. J. West Ortiz; Y. Rodríguez Reyes (Neotropical Entomology, 2020)

Cytotoxic Effect of Prodigiosin, Natural Red Pigment, Isolated from Serratia marcescens UFPEDA 398 - J. C. L. Lapenda; V. P. Alves; M. L. Adam; M. D. Rodrigues; S. C. Nascimento (Indian Journal of Microbiology, 2020)

Dog activity in protected areas: behavioral effects on mesocarnivores and the impacts of a top predator - Rita de Cassia Bianchi; Natalie Olifiers; Letícia Lutke Riski; Jéssica Abonízio Gouvea; Clarice Silva Cesário; Larissa Fornitano; Gisele Lamberti Zanirato; Mateus Yan de Oliveira; Kimberly Danielle Rodrigues de Morais; Renan Lieto Alves Ribeiro; Paulo Sergio D’Andrea; Matthew E. Gompper (European Journal of Wildlife Research, 2020)

Correction to: Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia Vieira; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2020)

Evidence of strong population bottleneck in genetics of endangered Brazilian Merganser (Mergus octosetaceus) - T. A. Maia; D. P. Campos; L. R. Silva; L. V. Lins; F. Ribeiro; F. Sebaio; F. R. Rodrigues; G. P. M. Dantas (Journal of Ornithology, 2020)

The Galactose-Binding Lectin Isolated from Vatairea macrocarpa Seeds Enhances the Effect of Antibiotics Against Staphylococcus aureus–Resistant Strain - Valdenice F. Santos; Maria S. Costa; Fábia F. Campina; Renato R. Rodrigues; Ana L. E. Santos; Felipe M. Pereira; Karla L. R. Batista; Rafael C. Silva; Raquel O. Pereira; Bruno A. M. Rocha; Henrique D. M. Coutinho; Claudener S. Teixeira (Probiotics and Antimicrobial Proteins, 2020)

Deleterious effects of chronic mercury exposure on in vitro LTP, memory process, and oxidative stress - Leandro F. Oliveira; Laís D. Rodrigues; Giancarlo M. Cardillo; Mariana B. Nejm; Marcia Guimarães-Marques; Selvin Z. Reyes-Garcia; Karolini Zuqui; Dalton V. Vassallo; Ana C. Fiorini; Carla A. Scorza; Fulvio A. Scorza (Environmental Science and Pollution Research, 2020)

Natural Vs Managed Habitat: Effect Over the Seed-Predator Pachymerus nucleorum and Its Natural Enemies - J O S Silva; M L E Costa; B S Paixão; J D B Macêdo; P M S Rodrigues; E M F Lins-Neto (Neotropical Entomology, 2020)

Increased Mmp/Reck Expression Ratio Is Associated with Increased Recognition Memory Performance in a Parkinson’s Disease Animal Model - Adauto Spindola; Adriano D. S. Targa; Lais Soares Rodrigues; Sheila Maria Brochado Winnischofer; Marcelo M. S. Lima; Mari Cleide Sogayar; Marina Trombetta-Lima (Molecular Neurobiology, 2020)

Using anticipatory life cycle assessment to enable future sustainable construction - Verena Göswein; Carla Rodrigues; José D. Silvestre; Fausto Freire; Guillaume Habert; Jakob König (Journal of Industrial Ecology, 2020)
The built environment is the largest single emitter of CO 2 and an important consumer of energy. Much research has gone into the improved efficiency of building operation and construction products. Life Cycle Assessment (LCA) is commonly used to assess existing buildings or building products. Classic LCA, however, is not suited for evaluating the environmental performance of developing technologies. A new approach, anticipatory LCA (a‐LCA), promises various advantages and can be used as a design constraint during the product development stage. It helps overcome four challenges: (i) data availability, (ii) stakeholder inclusion, (iii) risk assessment, and (iv) multi‐criteria problems. This article's contribution to the line of research is twofold: first, it adapts the a‐LCA approach for construction‐specific purposes in theoretical terms for the four challenges. Second, it applies the method to an innovative prefabricated modular envelope system, the CleanTechBlock (CTB), focusing on challenge (i). Thirty‐six CTB designs are tested and compared to conventional walls. Inclusion of technology foresight is achieved through structured scenario analysis. Moreover, challenge (iv) is tackled through the analysis of different environmental impact categories, transport‐related impacts, and thickness of the wall assemblies of the CTB. The case study results show that optimized material choice and product design is needed to reach the lowest environmental impact. Methodological findings highlight the importance of context‐specific solutions and the need for benchmarking new products.

Molecular characterization of a germplasm bank of Platonia insignis Mart.: a fruit tree - D. N. Pena; E. F. Moura; S. M. Rodrigues; M. S. P. Oliveira; J. P. Sanches; M. F. Moura (Genetic Resources and Crop Evolution, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Physiological and biochemical responses of soybean to white mold affected by manganese phosphite and fluazinam - M. I. C. Novaes; D. Debona; I. R. F. Fagundes-Nacarath; V. V. Brás; F. A. Rodrigues (Acta Physiologiae Plantarum, 2019)

Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Ecophysiology of mesophotic reef‐building corals in Hawai‘i is influenced by symbiont–host associations, photoacclimatization, trophic plasticity, and adaptation - Jacqueline L. Padilla‐Gamiño; Melissa S. Roth; Lisa J. Rodrigues; Christina J. Bradley; Robert R. Bidigare; Ruth D. Gates; Celia M. Smith; Heather L. Spalding (Limnology and Oceanography, 2019)
Mesophotic reef corals remain largely unexplored in terms of the genetic adaptations and physiological mechanisms to acquire, allocate, and use energy for survival and reproduction. In the Hawaiian Archipelago, the Leptoseris species complex form the most spatially extensive mesophotic coral ecosystem known and provide habitat for a unique community. To study how the ecophysiology of Leptoseris species relates to symbiont–host specialization and understand the mechanisms responsible for coral energy acquisition in extreme low light environments, we examined Symbiodinium (endosymbiotic dinoflagellate) photobiological characteristics and the lipids and isotopic signatures from Symbiodinium and coral hosts over a depth‐dependent light gradient (55–7 μ mol photons m −2 s −1 , 60–132 m). Clear performance differences demonstrate different photoadaptation and photoacclimatization across this genus. Our results also show that flexibility in photoacclimatization depends primarily on Symbiodinium type. Colonies harboring Symbiodinium sp. COI‐2 showed significant increases in photosynthetic pigment content with increasing depth, whereas colonies harboring Symbiodinium spp. COI‐1 and COI‐3 showed variability in pigment composition, yield measurements for photosystem II, as well as size and density of Symbiodinium cells. Despite remarkable differences in photosynthetic adaptive strategies, there were no significant differences among lipids of Leptoseris species with depth. Finally, isotopic signatures of both host and Symbiodinium changed with depth, indicating that coral colonies acquired energy from different sources depending on depth. This study highlights the complexity in physiological adaptations within this symbiosis and the different strategies used by closely related mesophotic species to diversify energy acquisition and to successfully establish and compete in extreme light‐limited environments.

Occurrence and Environmental Distribution of 5 UV Filters During the Summer Season in Different Water Bodies - S. K. Fagervold; A. S. Rodrigues; C. Rohée; R. Roe; M. Bourrain; D. Stien; P. Lebaron (Water, Air, & Soil Pollution, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Early Interaction of Alternaria infectoria Conidia with Macrophages - M. C. Almeida; D. Antunes; B. M. A. Silva; L. Rodrigues; M. Mota; O. Borges; C. Fernandes; T. Gonçalves (Mycopathologia, 2019)

Paraclostridium is the Main Genus of Anaerobic Bacteria Isolated from New Species of the Marine Sponge Plakina in the Brazilian Southeast Coast - Bruno Francesco Rodrigues de Oliveira; Mellissa D’Avila Cavalcanti; Suzanne de Oliveira Nunes; Leandro Araujo Lobo; Regina Maria Cavalcanti Pilotto Domingues; Guilherme Muricy; Marinella Silva Laport (Current Microbiology, 2019)

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

Geostatistical stationary space-time covariance functions modeling of Yellow Sigatoka progress in banana crop - J. D. P. Rodrigues; M. C. Alves; A. S. Freitas; E. A. Pozza; M. S. Oliveira; H. J. P. Alves (Australasian Plant Pathology, 2019)

Resource partitioning between two young‐of‐year cownose rays Rhinoptera bonasus and R. brasiliensis within a communal nursery inferred by trophic biomarkers - Bianca de Sousa Rangel; Nigel E. Hussey; Aline D. Gomes; Alexandre Rodrigues; Luiz A. Martinelli; Renata Guimarães Moreira (Journal of Fish Biology, 2019)
Although interspecific trophic interactions plays a principal role within elasmobranch communal nurseries, little is known over variation in foraging strategies adopted by young‐of‐year of sympatric species. To test the hypothesis of dietary resource partitioning between batoids within a communal nursery, we investigated two cownose ray species, Rhinoptera bonasus and R. brasiliensis , which occur in heterospecific groups, a strategy predicted to increase survival and foraging success. Using two biochemical tracers, fatty acids (FA) and stable isotopes (δ 15 N and δ 13 C), the combined effects of maternal investment and the formation of heterospecific groups implying competition for, or partitioning of available food resources were investigated. Through univariate and multivariate analyses of biochemical tracers in several tissues (fin clip, muscle, liver, red blood cells; RBC) and plasma, our results revealed significant interspecific differences in tracers between the two species. Total FAs (∑saturated FA, ∑monounsaturated FA and ∑polyunsaturated FA) and trophic biomarkers ( i.e ., docosahexaenoic acid, arachidonic acid, oleic acid and δ 15 N) were the principle tracers responsible for the differences detected. These data revealed that R. brasiliensis was less enriched in physiologically important essential FAs than R. bonasus . Our findings suggest that these congeneric species differ in maternal investment strategy and moderately partition food resources over relatively fine spatial scales within a single nursery habitat to limit competition. These results provide further knowledge on the foraging strategies adopted by batoids in communal nursery areas, information that is required for improving spatial conservation and management planning.

Pyrene degradation by marine-derived ascomycete: process optimization, toxicity, and metabolic analyses - Maria R. S. Vasconcelos; Gabriela A. L. Vieira; Igor V. R. Otero; Rafaella C. Bonugli-Santos; Marili V. N. Rodrigues; Vera L. G. Rehder; Milene Ferro; Sinésio Boaventura; Maurício Bacci; Lara D. Sette (Environmental Science and Pollution Research, 2019)

Chemical characterisation of the constituents of Eugenia protenta McVaugh and leishmanicidal activity of dimethylxanthoxylin - Flávio N. Sarges; Márcia M. Cascaes; Lienne S. Moraes; Giselle M. S. P. Guilhon; Edilene O. Silva; Maria das Graças B. Zoghbi; Eloisa H. A. Andrade; Ana Paula D. Rodrigues; Brenda F. Costa; Rayssa N. M. Figueiredo (Natural Product Research, 2019)

Correction to: Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. G. Coelho; G. V. Tolesano-Pascoli; V. S. Rodrigues; M. P. J. Szabó; V. N. Ramos (Tropical Animal Health and Production, 2019)

Regulation of cell wall development in Brachypodium distachyon in vitro as affected by cytokinin and gas exchange - T. C. Mamedes-Rodrigues; D. S. Batista; T. A. Napoleão; E. A. Fortini; A. C. F. Cruz; M. G. C. Costa; W. C. Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Dopaminergic Lesion in the Olfactory Bulb Restores Olfaction and Induces Depressive-Like Behaviors in a 6-OHDA Model of Parkinson’s Disease - Jessica L. Ilkiw; Luana C. Kmita; Adriano D. S. Targa; Ana Carolina D. Noseda; Lais S. Rodrigues; Flávia W. C. Dorieux; Juliane Fagotti; Patrícia dos Santos; Marcelo M. S. Lima (Molecular Neurobiology, 2019)

Lagged Population Growth in a Termite Host Colony: Cause or Consequence of Inquilinism? - V B Rodrigues; D A Costa; P F Cristaldo; O DeSouza (Neotropical Entomology, 2018)

Application of the Fenton’s process in a bubble column reactor for hydroquinone degradation - Vanessa N. Lima; Carmen S. D. Rodrigues; Luis M. Madeira (Environmental Science and Pollution Research, 2018)

Synthetic olive mill wastewater treatment by Fenton’s process in batch and continuous reactors operation - Bruno M. Esteves; Carmen S. D. Rodrigues; Luís M. Madeira (Environmental Science and Pollution Research, 2018)

Surviving in hot and cold: psychrophiles and thermophiles from Deception Island volcano, Antarctica - Amanda G. Bendia; Gabriel G. Araujo; André A. Pulschen; Bruna Contro; Rubens T. D. Duarte; Fábio Rodrigues; Douglas Galante; Vivian H. Pellizari (Extremophiles, 2018)

Phosphites attenuate Sclerotinia sclerotiorum-induced physiological impairments in common bean - I. R. F. Fagundes-Nacarath; D. Debona; V. V. Brás; P. R. Silveira; F. A. Rodrigues (Acta Physiologiae Plantarum, 2018)

Histopathological Evaluation of Combined Impacts of the Synthetic Progestin Levonorgestrel and Temperature on the Female Zebrafish Maturation Using a Semi-quantitative Grading Analysis—Is it Enough? - P. G. Cardoso; D. Rodrigues; T. V. Madureira; M. J. Rocha; E. Rocha (Bulletin of Environmental Contamination and Toxicology, 2018)

In Vivo Determination of Moisturizers Efficacy on Human Skin Hydration by Confocal Raman Spectroscopy - Vamshi Krishna Tippavajhala; Taciana D. Magrini; Daniele C. Matsuo; Michely G. P. Silva; Priscila P. Favero; Leonardo Rodrigues De Paula; Airton Abrahão Martin (AAPS PharmSciTech, 2018)

Front Cover - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)

Functional diversity mediates macroecological variation in plant–hummingbird interaction networks - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)
Aim Species interaction networks are known to vary in structure over large spatial scales. We investigated the hypothesis that environmental factors affect interaction network structure by influencing the functional diversity of ecological communities. Notably, we expect more functionally diverse communities to form interaction networks with a higher degree of niche partitioning. Location: Americas. Time period: Current. Major taxa studied: Hummingbirds and their nectar plants. Methods We used a large dataset comprising 74 quantitative plant–hummingbird interaction networks distributed across the Americas, along with morphological trait data for 158 hummingbird species. First, we used a model selection approach to evaluate associations between the environment (climate, topography and insularity), species richness and hummingbird functional diversity as predictors of network structure (niche partitioning, i.e., complementary specialization and modularity). Second, we used structural equation models (SEMs) to ask whether environmental predictors and species richness affect network structure directly and/or indirectly through their influence on hummingbird functional diversity. For a subset of 28 networks, we additionally evaluated whether plant functional diversity was associated with hummingbird functional diversity and network structure. Results Precipitation, insularity and plant richness, together with hummingbird functional diversity (specifically, functional dispersion), were consistently strong predictors of niche partitioning in plant–hummingbird networks. Moreover, SEMs showed that environmental predictors and plant richness affected network structure both directly and indirectly through their effects on hummingbird functional diversity. Plant functional diversity, however, was unrelated to hummingbird functional diversity and network structure. Main conclusions: We reveal the importance of hummingbird functional diversity for niche partitioning in plant–hummingbird interaction networks. The lack of support for similar effects for plant functional diversity potentially indicates that consumer functional diversity might be more important for structuring interaction networks than resource functional diversity. Changes in pollinator functional diversity are therefore likely to alter the structure of interaction networks and associated ecosystem functions.

Gaseous and liquid effluents treatment in bubble column reactors by advanced oxidation processes: A review - Vanessa N. Lima; Carmen S. D. Rodrigues; Ricardo A. C. Borges; Luis M. Madeira (Critical Reviews in Environmental Science and Technology, 2018)

The Híbrido de Timor germplasm: identification of molecular diversity and resistance sources to coffee berry disease and leaf rust - R. A. Silva; L. Zambolim; I. S. L. Castro; H. S. Rodrigues; C. D. Cruz; E. T. Caixeta (Euphytica, 2018)

Combined effects of insecticide exposure and predation risk on freshwater detritivores - Andreia C. M. Rodrigues; Maria D. Bordalo; Oksana Golovko; Olga Koba; Carlos Barata; Amadeu M. V. M. Soares; João L. T. Pestana (Ecotoxicology, 2018)

Mitochondrial genome analysis in penile carcinoma - L. F. Araujo; A. T. Terra; C. T. G. Sares; C. F. R. Sobreira; E. F. Faria; R. D. Machado; A. A. Rodrigues; V. F. Muglia; W. A. Silva; R. B. Reis (Molecular Biology Reports, 2018)

Targeting the mitochondrial VDAC in hepatocellular carcinoma using a polyclonal antibody-conjugated to a nitrosyl ruthenium complex - Loyanne C. B. Ramos; Fernando P. Rodrigues; Juliana C. Biazzotto; Sergio de Paula Machado; Leonardo D. Slep; Michael R. Hamblin; Roberto S. da Silva (JBIC Journal of Biological Inorganic Chemistry, 2018)

Is Vitamin D3 Transdermal Formulation Feasible? An Ex Vivo Skin Retention and Permeation - Gabriela Maria D’Angelo Costa; Claudinéia Aparecida Sales de Oliveira Pinto; Vânia Rodrigues Leite-Silva; André Rolim Baby; Maria Valéria Robles Velasco (AAPS PharmSciTech, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

A Note on the Magnitude of the Feedback Effect in Environmentally Extended Multi‐Region Input‐Output Tables - Daniel Moran; Richard Wood; João F. D. Rodrigues (Journal of Industrial Ecology, 2018)
Summary Global multiregion input‐output (MRIO) tables have been developed to capture international spillover effects due to demand in one country and production in other countries. International spillovers have been growing and have become so dominant, especially in environmental analysis, that their inclusion is essential when analyzing impacts of consumption. MRIO tables give full coverage of the world economy, but do not always respect the official data of a given country. When international spillovers also cause increased production in the country of demand, we see what are known as “feedback effects.” As coupled models are being developed that make use of an official foreground national input‐output table (IOT) alongside an existing global MRIO, we are left in the situation where a coupled model does not use the official foreground information when modeling international feedback loops. The question thus arises: How large are these feedback loops for different environmental impacts? We look specifically at the amount of domestic production that is embodied in imports back into that region. We find that for emissions, the feedbacks are small, usually <2% of the total import footprint, though up to 6%+ for some countries in some years for some stressors. Our findings suggest that using Leontief multipliers from available MRIOs may be an acceptable method for modeling imports into national IOTs for environmentally extended MRIO analysis.

Lignin and cellulose synthesis and antioxidative defense mechanisms are affected by light quality in Brachypodium distachyon - T. C. Mamedes-Rodrigues; D. S. Batista; T. A. Napoleão; A. C. F. Cruz; E. A. Fortini; F. T. S. Nogueira; E. Romanel; W. C. Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Regenerative potential, metabolic profile, and genetic stability of Brachypodium distachyon embryogenic calli as affected by successive subcultures - T. C. Mamedes-Rodrigues; D. S. Batista; N. M. Vieira; E. M. Matos; D. Fernandes; A. Nunes-Nesi; C. D. Cruz; L. F. Viccini; F. T. S. Nogueira; W. C. Otoni (Protoplasma, 2018)

First Report on vanA-Enterococcus faecalis Recovered from Soils Subjected to Long-Term Livestock Agricultural Practices in Azores Archipelago - Vanessa Silva; Fernando Peixoto; Gilberto Igrejas; Carolina Parelho; Patrícia Garcia; Isabel Carvalho; Margarida Sousa; José Eduardo Pereira; Armindo Rodrigues; Patrícia Alexandra Curado Quintas D Poeta (International Journal of Environmental Research, 2018)

Author Correction: Ouabain attenuates ovalbumin-induced airway inflammation - José Guilherme F. M. Galvão; Luiz Henrique Agra Cavalcante-Silva; Deyse Cristina M. Carvalho; Laércia Karla D. P. Ferreira; Talissa Mozzini Monteiro; Adriano Francisco Alves; Larissa Adiles M. P. Ferreira; Francisco Allysson A. F. Gadelha; Marcia Regina Piuvezam; Sandra Rodrigues-Mascarenhas (Inflammation Research, 2018)

Tingenone, a pentacyclic triterpene, induces peripheral antinociception due to cannabinoid receptors activation in mice - C. C. Veloso; R. C. M. Ferreira; V. G. Rodrigues; L. P. Duarte; A. Klein; I. D. Duarte; T. R. L. Romero; A. C. Perez (Inflammopharmacology, 2018)

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

Organosulfur compound protects against memory decline induced by scopolamine through modulation of oxidative stress and Na+/K+ ATPase activity in mice - Fernanda D. da Silva; Mikaela P. Pinz; Renata L. de Oliveira; Karline C. Rodrigues; Francine R. Ianiski; Mariana M. Bassaco; Claudio C. Silveira; Cristiano R. Jesse; Silvane S. Roman; Ethel A. Wilhelm; Cristiane Luchese (Metabolic Brain Disease, 2017)

Ouabain attenuates ovalbumin-induced airway inflammation - José Guilherme F. M. Galvão; Luiz Henrique Agra Cavalcante-Silva; Deyse Cristina M. Carvalho; Laércia Karla D. P. Ferreira; Talissa Mozzini Monteiro; Adriano Francisco Alves; Larissa Adilis M. P. Ferreira; Francisco Allysson A. F. Gadelha; Marcia Regina Piuvezam; Sandra Rodrigues-Mascarenhas (Inflammation Research, 2017)

Diversity and succession of pelagic microorganism communities in a newly restored Illinois River floodplain lake - Michael J. Lemke; Sara F. Paver; Keenan E. Dungey; Luiz Felipe M. Velho; Angela D. Kent; Luzia Cleide Rodrigues; Doyn M. Kellerhals; Michelle R. Randle (Hydrobiologia, 2017)

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

New cytotoxic furan from the marine sediment-derived fungi Aspergillus niger - Paula Karina S. Uchoa; Antonia T. A. Pimenta; Raimundo Braz-Filho; Maria da Conceição F. de Oliveira; Natália N. Saraiva; Barbara S. F. Rodrigues; Ludwig H. Pfenning; Lucas M. Abreu; Diego V. Wilke; Katharine G. D. Florêncio; Mary Anne S. Lima (Natural Product Research, 2017)

Physiological responses of reared sea bream ( Sparus aurata Linnaeus, 1758) to an Amyloodinium ocellatum outbreak - M Moreira; D Schrama; F Soares; T Wulff; P Pousão‐Ferreira; P Rodrigues (Journal of Fish Diseases, 2017)
Amyloodiniosis represents a major bottleneck for semi‐intensive aquaculture production in Southern Europe, causing extremely high mortalities. Amyloodinium ocellatum is a parasitic dinoflagellate that can infest almost all fish, crustacean and bivalves that live within its ecological range. Fish mortalities are usually attributed to anoxia, associated with serious gill hyperplasia, inflammation, haemorrhage and necrosis in heavy infestations; or with osmoregulatory impairment and secondary microbial infections due to severe epithelial damage in mild infestation. However, physiological information about the host responses to A. ocellatum infestation is scarce. In this work, we analysed the proteome of gilthead sea bream ( Sparus aurata ) plasma and relate it with haematological and immunological indicators, in order to enlighten the different physiological responses when exposed to an A. ocellatum outbreak. Using 2D‐ DIGE , immunological and haematological analysis and in response to the A. ocellatum contamination we have identified several proteins associated with acute‐phase response, inflammation, lipid transport, homoeostasis, and osmoregulation, wound healing, neoplasia and iron transport. Overall, this preliminary study revealed that amyloodiniosis affects some fish functional pathways as revealed by the changes in the plasma proteome of S. aurata, and that the innate immunological system is not activated in the presence of the parasite.

Wax Removal and Diamondback Moth Performance in Collards Cultivars - G. A. Silva; R. M. Pereira; N. Rodrigues-Silva; T. C. Souza; D. O. Ferreira; E. A. Queiroz; G. A. R. Silva; M. C. Picanço (Neotropical Entomology, 2017)

Cholinergic Oculomotor Nucleus Activity Is Induced by REM Sleep Deprivation Negatively Impacting on Cognition - Patrícia Dos Santos; Adriano D. S. Targa; Ana Carolina D. Noseda; Lais S. Rodrigues; Juliane Fagotti; Marcelo M. S. Lima (Molecular Neurobiology, 2017)

Chronic Treatment with Paraquat Induces Brain Injury, Changes in Antioxidant Defenses System, and Modulates Behavioral Functions in Zebrafish - Mauro E. Nunes; Talise E. Müller; Marcos M. Braga; Barbara D. Fontana; Vanessa A. Quadros; Aline Marins; Cíntia Rodrigues; Charlene Menezes; Denis B. Rosemberg; Vania Lucia Loro (Molecular Neurobiology, 2017)

Informativeness of patient initial reports of adverse drug reactions. Can it be improved by a pharmacovigilance centre? - F Kheloufi; A Default; F Rouby; D Laugier-Castellan; M Boyer; B Rodrigues; J Ponte-Astoul; MJ Jean-Pastor; O Blin; J Micallef (European Journal of Clinical Pharmacology, 2017)

Acute liver effects, disposition and metabolic fate of [14C]-fenclozic acid following oral administration to normal and bile-cannulated male C57BL/6J mice - Kathryn Pickup; Scott Martin; Elizabeth A. Partridge; Huw B. Jones; Jonathan Wills; Tim Schulz-Utermoehl; Alan McCarthy; Alison Rodrigues; Chris Page; Kerry Ratcliffe; Sunil Sarda; Ian D. Wilson (Archives of Toxicology, 2017)

Larval development and allometric growth of the black‐faced blenny Tripterygion delaisi - F. N. Solomon; D. Rodrigues; E. J. Gonçalves; E. A. Serrão; R. Borges (Journal of Fish Biology, 2017)
Larval development and allometric growth patterns of the black‐faced blenny Tripterygion delaisi are described from a larval series (body length, L B = 3·30–12·10 mm) caught by light traps at the Arrábida Marine Park, Portugal. Larvae of T. delaisi possess distinctive morphometric and meristic characteristics which can be used to identify this species from related taxa. Pigmentation is sparse but characteristic, consisting of pigmented eyes, gas bladder pigmentation in the dorsal region, anal pigmentation and a row of regularly spaced postanal ventral melanophores. This pattern is present from as early as the yolk‐sac stage and persists throughout all stages with just the addition of head and caudal pigmentation during the flexion and postflexion stages, respectively. The majority of fin development (with the exception of the caudal fin), occurs in the later stages of development. Myomere counts range between 37 and 45 for all stages. Growth is allometric during larval development. When inflexion points of growth were detected, growth was found to be biphasic with the inflexion points occurring within a very narrow range of L B (8·70–8·90 mm) close to the mean ± s.d. (9·44 ± 1·48 mm L B ) of postflexion larvae. Considering allometric growth patterns and ontogenetic descriptions together, the first developmental phase includes the preflexion and flexion stage larvae, while the second phase characterises the postflexion larvae prior to the transition from larvae to juvenile.

Application of solar photo-Fenton toward toxicity removal and textile wastewater reuse - Maria Clara V. M. Starling; Paulo Henrique Rodrigues dos Santos; Felipe Antônio Ribeiro de Souza; Sílvia Corrêa Oliveira; Mônica M. D. Leão; Camila C. Amorim (Environmental Science and Pollution Research, 2017)

Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. C. Gonçalves; G. V. Tolesano; V. S. Rodrigues; M. P. J. Szabó (Tropical Animal Health and Production, 2017)

Genetic characterization of residual Triatoma infestans populations from Brazil by microsatellite - Carlota Josefovicz Belisário; Grasielle Caldas D’Avila Pessoa; Eduardo Melos Silva; Aline Cristine Luiz Rosa; Rafaela Elias Ferreira; Cleonara Bedin; Tania Wilhelms; Fernanda de Mello; Helder Silveira Coutinho; Eduardo Lins Oyama Fonseca; Roberto Fonseca dos Santos; Vera Lucia Cortiço Corrêa Rodrigues; et al. (Genetica, 2017)

Multibiomarker responses in aquatic insect Belostoma elegans (Hemiptera) to organic pollution in freshwater system - S. Lavarías; C. Ocon; V. López van Oosterom; A. Laino; D. A. Medesani; A. Fassiano; H. Garda; J. Donadelli; M. Ríos de Molina; A. Rodrigues Capítulo (Environmental Science and Pollution Research, 2017)

Performance of Eriopis connexa (Coleoptera: Coccinellidae) resistant to lambda-cyhalothrin after extended recovery from knockdown - D S Santos; A R S Rodrigues; J B Torres; R Lira (Neotropical Entomology, 2016)

An Input‐Output Model of Extended Producer Responsibility - João F. D. Rodrigues; António Lorena; Inês Costa; Paulo Ribeiro; Paulo Ferrão (Journal of Industrial Ecology, 2016)
Summary Under an extended producer responsibility (EPR) system, when a producer delivers a product to the market it must also pay a takeback fee, which is used to cover the costs of end‐of‐life disposal. EPR systems are currently used in Europe and beyond to manage a variety of products, including packaging and used tires. In this article we develop an input‐output (IO) model that is able to assess the impacts of an EPR system, and is based on the waste IO (WIO) model. The WIO model is itself a hybrid‐unit model extension of the Leontief model that is able to capture the substitution effect between recycled/recovered material/energy from waste treatment and their non‐waste cognates. The resulting EPRIO model, besides the conventional direct and indirect effects of the Leontief model and the substitution effects of the WIO model, is able to capture the opportunity costs of financing the EPR system, and additionally requires the specification of an alternative waste management policy, with its own opportunity costs. The impact of an EPR policy is thus the difference between the impacts of the reference EPR and the alternative waste treament policies. The resulting model is illustrated with a simple example of a used tire management EPR system.

Contrasting factors drive within-lake bacterial community composition and functional traits in a large shallow subtropical lake - Marla Sonaira Lima; David da Motta Marques; Ng Haig They; Katherine D. McMahon; Lúcia Ribeiro Rodrigues; Luciana de Souza Cardoso; Luciane Oliveira Crossetti (Hydrobiologia, 2016)

Modulation of aquaporins 3 and 9 after exposure of ovine ovarian tissue to cryoprotectants followed by in vitro culture - A. D. Sales; A. B. G. Duarte; R. R. Santos; K. A. Alves; L. F. Lima; G. Q. Rodrigues; I. R. Brito; C. H. Lobo; J. B. Bruno; Y. Locatelli; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Research, 2016)

A spatially explicit estimate of the prewhaling abundance of the endangered North Atlantic right whale - Sophie Monsarrat; M. Grazia Pennino; Tim D. Smith; Randall R. Reeves; Christine N. Meynard; David M. Kaplan; Ana S.L. Rodrigues (Conservation Biology, 2016)
The North Atlantic right whale (NARW) (Eubalaena glacialis) is one of the world's most threatened whales. It came close to extinction after nearly a millennium of exploitation and currently persists as a population of only approximately 500 individuals. Setting appropriate conservation targets for this species requires an understanding of its historical population size, as a baseline for measuring levels of depletion and progress toward recovery. This is made difficult by the scarcity of records over this species’ long whaling history. We sought to estimate the preexploitation population size of the North Atlantic right whale and understand how this species was distributed across its range. We used a spatially explicit data set on historical catches of North Pacific right whales (NPRWs) (Eubalaena japonica) to model the relationship between right whale relative density and the environment during the summer feeding season. Assuming the 2 right whale species select similar environments, we projected this model to the North Atlantic to predict how the relative abundance of NARWs varied across their range. We calibrated these relative abundances with estimates of the NPRW total prewhaling population size to obtain high and low estimates for the overall NARW population size prior to exploitation. The model predicted 9,075–21,328 right whales in the North Atlantic. The current NARW population is thus

Using the mini-VIDAS® Easy Salmonella protocol to assess contamination in transitional and coastal waters - M. J. Rodrigues; K. Martins; D. Garcia; S. M. F. Ferreira; S. C. Gonçalves; S. Mendes; M. F. L. Lemos (Archives of Microbiology, 2016)

Exposure to different glyphosate formulations on the oxidative and histological status of Rhamdia quelen - Camila R. Murussi; Maiara D. Costa; Jossiele W. Leitemperger; Luciana Guerra; Cintia C. R. Rodrigues; Charlene C. Menezes; Eduardo S. Severo; Fábio Flores-Lopes; Joseânia Salbego; Vania L. Loro (Fish Physiology and Biochemistry, 2016)

The macroecology of phylogenetically structured hummingbird–plant networks - Ana M. Martín González; Bo Dalsgaard; David Nogués‐Bravo; Catherine H. Graham; Matthias Schleuning; Pietro K. Maruyama; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Severino Mendes de Azevedo; Andrea C. Baquero; et al. (Global Ecology and Biogeography, 2015)
Aim To investigate the association between hummingbird–plant network structure and species richness, phylogenetic signal on species' interaction pattern, insularity and historical and current climate. Location Fifty‐four communities along a c . 10,000 km latitudinal gradient across the A mericas (39° N –32° S ), ranging from sea level to c . 3700 m a.s.l., located on the mainland and on islands and covering a wide range of climate regimes. Methods We measured the level of specialization and modularity in mutualistic plant–hummingbird interaction networks. Using an ordinary least squares multimodel approach, we examined the influence of species richness, phylogenetic signal, insularity and current and historical climate conditions on network structure (null‐model‐corrected specialization and modularity). Results Phylogenetically related species, especially plants, showed a tendency to interact with a similar array of mutualistic partners. The spatial variation in network structure exhibited a constant association with species phylogeny ( R 2 = 0.18–0.19); however, network structure showed the strongest association with species richness and environmental factors ( R 2 = 0.20–0.44 and R 2 = 0.32–0.45, respectively). Specifically, higher levels of specialization and modularity were associated with species‐rich communities and communities in which closely related hummingbirds visited distinct sets of flowering species. On the mainland, specialization was also associated with warmer temperatures and greater historical temperature stability. Main conclusions Our results confirm the results of previous macroecological studies of interaction networks which have highlighted the importance of species richness and the environment in determining network structure. Additionally, for the first time, we report an association between network structure and species phylogenetic signal at a macroecological scale, indicating that high specialization and modularity are associated with high interspecific competition among closely related hummingbirds, subdividing the floral niche. This suggests a tighter co‐evolutionary association between hummingbirds and their plants than in previously studied plant–bird mutualistic systems.

The Size But not the Symmetry of the Wings of Eulaema nigrita Lepeletier (Apidae: Euglossini) is Affected by Human-Disturbed Landscapes in the Brazilian Cerrado Savanna - N S Pinto; D P Silva; J G Rodrigues; P De Marco (Neotropical Entomology, 2015)

Oxidative stress markers in fish (Astyanax sp. and Danio rerio) exposed to urban and agricultural effluents in the Brazilian Pampa biome - D. G. Costa-Silva; M. E. M Nunes; G. L. Wallau; I. K. Martins; A. P. P Zemolin; L. C. Cruz; N. R. Rodrigues; A. R. Lopes; T. Posser; J. L. Franco (Environmental Science and Pollution Research, 2015)

Ecological literacy and beyond: Problem-based learning for future professionals - Thomas M. Lewinsohn; José Luiz Attayde; Carlos Roberto Fonseca; Gislene Ganade; Leonardo Ré Jorge; Johannes Kollmann; Gerhard E. Overbeck; Paulo Inácio Prado; Valério D. Pillar; Daniela Popp; Pedro L. B. da Rocha; Wesley Rodrigues Silva; et al. (Ambio, 2015)

Ingestive behavior of grazing steers fed increasing levels of concentrate supplementation with different crude protein contents - Fabrício Bacelar Lima Mendes; Robério Rodrigues Silva; Gleidson Giordano Pinto de Carvalho; Fabiano Ferreira da Silva; Túlio Otávio Jardim D`Almeida Lins; Anderson Luiz Nascimento da Silva; Venício Macedo; George Abreu Filho; Sinvaldo Oliveira de Souza; Joanderson Oliveira Guimarães (Tropical Animal Health and Production, 2015)

REM Sleep Deprivation Reverses Neurochemical and Other Depressive-Like Alterations Induced by Olfactory Bulbectomy - Maira J. Maturana; Cláudia Pudell; Adriano D. S. Targa; Laís S. Rodrigues; Ana Carolina D. Noseda; Mariana H. Fortes; Patrícia dos Santos; Cláudio Da Cunha; Sílvio M. Zanata; Anete C. Ferraz; Marcelo M. S. Lima (Molecular Neurobiology, 2015)

Solar photocatalytic gas-phase degradation of n-decane—a comparative study using cellulose acetate monoliths coated with P25 or sol-gel TiO2 films - Sandra M. Miranda; Filipe V. S. Lopes; Caio Rodrigues-Silva; Susana D. S. Martins; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2015)

Modelling the risk of invasion by the red-swamp crayfish (Procambarus clarkii): incorporating local variables to better inform management decisions - Francisco D. Moreira; Fernando Ascensão; César Capinha; Diana Rodrigues; Pedro Segurado; Margarida Santos-Reis; Rui Rebelo (Biological Invasions, 2015)

Bacterial diversity assessment in soil of an active Brazilian copper mine using high-throughput sequencing of 16S rDNA amplicons - Viviane D. Rodrigues; Tatiana T. Torres; Laura M. M. Ottoboni (Antonie van Leeuwenhoek, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Early postnatal, but not late, exposure to chemical ambient pollutant 1,2-naphthoquinone increases susceptibility to pulmonary allergic inflammation at adulthood - Karen T. Santos; Juliana Florenzano; Leandro Rodrigues; Rodolfo R. Fávaro; Fernanda F. Ventura; Marcela G. Ribeiro; Simone A. Teixeira; Heloisa H. A. Ferreira; Susan D. Brain; Amílcar S. Damazo; Telma M. Zorn; Niels O. Câmara; et al. (Archives of Toxicology, 2014)

Light and temperature induce variations in the density and ultrastructure of the secretory spaces in the diesel-tree (Copaifera langsdorffii Desf.—Leguminosae) - T. M. Rodrigues; P. F. S. M. Buarque; A. G. Coneglian; D. C. Reis (Trees, 2014)

Increasing the Added-Value of Onions as a Source of Antioxidant Flavonoids: A Critical Review - M. R. Pérez-Gregorio; J. Regueiro; J. Simal-Gándara; A. S. Rodrigues; D. P. F. Almeida (Critical Reviews in Food Science and Nutrition, 2014)

Metabolism, Intake, and Digestibility of Lambs Supplemented with Organic Chromium - Jose Francisco Xavier da Rocha; Adelina Rodrigues Aires; Matheus Augusto Gonçalves Nunes; Erico Marlon Moraes Flores; Gilberto Vilmar Kozloski; Agueda Castagna de Vargas; Luana D’Avila Farias; Marcelo da Silva Cecim; Marta Lizandra do Rego Leal (Biological Trace Element Research, 2013)

Flight responses of Sitotroga cerealella (Lepidoptera: Gelechiidae) to corn kernel volatiles in a wind tunnel - Hany Ahmed Fouad; Lêda Rita D’Antonino Faroni; Evaldo Ferreira Vilela; Eraldo Rodrigues de Lima (Arthropod-Plant Interactions, 2013)

Effect of magnetic hyperthermia on the structure of biofilm and cellular viability of a food spoilage bacterium - D. Rodrigues; M. Bañobre-López; B. Espiña; J. Rivas; J. Azeredo (Biofouling, 2013)

Isolation and characterization of rice (Oryza sativa L.) E3-ubiquitin ligase OsHOS1 gene in the modulation of cold stress response - Tiago Lourenço; Helena Sapeta; Duarte D. Figueiredo; Mafalda Rodrigues; André Cordeiro; Isabel A. Abreu; Nelson J. M. Saibo; M. Margarida Oliveira (Plant Molecular Biology, 2013)

Biological impacts of ocean acidification: a postgraduate perspective on research priorities - Samantha L. Garrard; R. C. Hunter; A. Y. Frommel; A. C. Lane; J. C. Phillips; R. Cooper; R. Dineshram; U. Cardini; S. J. McCoy; M. Arnberg; B. G. Rodrigues Alves; S. Annane; et al. (Marine Biology, 2013)

In vitro exploration of potential mechanisms of toxicity of the human hepatotoxic drug fenclozic acid - Alison V. M. Rodrigues; Helen E. Rollison; Scott Martin; Sunil Sarda; Timothy Schulz-Utermoehl; Simone Stahl; Frida Gustafsson; Julie Eakins; J. Gerry Kenna; Ian D. Wilson (Archives of Toxicology, 2013)

Characterization of water and wildlife strains as a subgroup of C ampylobacter jejuni using DNA microarrays - Richard A. Stabler; Jonas T. Larsson; Suaad Al‐Jaberi; Eva M. Nielsen; Emily Kay; Clarence C. Tam; Craig D. Higgins; Laura C. Rodrigues; Judith F. Richardson; Sarah J. O'Brien; Brendan W. Wren (Environmental Microbiology, 2013)
Summary C ampylobacter jejuni is the leading cause of human bacterial gastroenteritis worldwide, but source attribution of the organism is difficult. Previously, DNA microarrays were used to investigate isolate source, which suggested a non‐livestock source of infection. In this study we analysed the genome content of 162 clinical, livestock and water and wildlife ( WW ) associated isolates combined with the previous study. Isolates were grouped by genotypes into nine clusters ( C 1 to C 9). Multilocus sequence typing ( MLST ) data demonstrated that livestock associated clonal complexes dominated clusters C 1– C 6. The majority of WW isolates were present in the C 9 cluster. Analysis of previously reported genomic variable regions demonstrated that these regions were linked to specific clusters. Two novel variable regions were identified. A six gene multiplex PCR ( mPCR ) assay, designed to effectively differentiated strains into clusters, was validated with 30 isolates. A further five WW isolates were tested by m PCR and were assigned to the C 7‐ C 9 group of clusters. The predictive mPCR test could be used to indicate if a clinical case has come from domesticated or WW sources. Our findings provide further evidence that WW C . jejuni subtypes show niche adaptation and may be important in causing human infection.

Systematics of spiny‐backed treefrogs ( H ylidae: O steocephalus ): an A mazonian puzzle - Karl‐Heinz Jungfer; Julián Faivovich; José M. Padial; Santiago Castroviejo‐Fisher; Mariana M. Lyra; Bianca V. M. Berneck; Patricia P. Iglesias; Philippe J. R. Kok; Ross D. MacCulloch; Miguel T. Rodrigues; Vanessa K. Verdade; Claudia P. Torres Gastello; et al. (Zoologica Scripta, 2013)
Spiny‐backed tree frogs of the genus O steocephalus are conspicuous components of the tropical wet forests of the A mazon and the G uiana S hield. Here, we revise the phylogenetic relationships of O steocephalus and its sister group T epuihyla , using up to 6134 bp of DNA sequences of nine mitochondrial and one nuclear gene for 338 specimens from eight countries and 218 localities, representing 89% of the 28 currently recognized nominal species. Our phylogenetic analyses reveal (i) the paraphyly of O steocephalus with respect to T epuihyla , (ii) the placement of ‘ H yla’ warreni as sister to T epuihyla , (iii) the non‐monophyly of several currently recognized species within O steocephalus and (iv) the presence of low ( O . taurinus and O . oophagus ) for the 16 S gene fragment used in amphibian DNA barcoding. We propose a new taxonomy, securing the monophyly of O steocephalus and T epuihyla by rearranging and redefining the content of both genera and also erect a new genus for the sister group of O steocephalus . The colouration of newly metamorphosed individuals is proposed as a morphological synapomorphy for O steocephalus . We recognize and define five monophyletic species groups within O steocephalus , synonymize three species of O steocephalus ( O . germani , O . phasmatus and O . vilmae ) and three species of T epuihyla ( T . celsae , T . galani and T . talbergae ) and reallocate three species ( H yla helenae to O steocephalus , O . exophthalmus to T epuihyla and O . pearsoni to D ryaderces gen. n.). Furthermore, we flag nine putative new species (an increase to 138% of the current diversity). We conclude that species numbers are largely underestimated, with most hidden diversity centred on widespread and polymorphic nominal species. The evolutionary origin of breeding strategies within O steocephalus is discussed in the light of this new phylogenetic hypothesis, and a novel type of amplexus (gular amplexus) is described.

Are all eggs created equal? A case study from the Hawaiian reef-building coral Montipora capitata - Jacqueline L. Padilla-Gamiño; Robert R. Bidigare; Daniel J. Barshis; Ada Alamaru; Laetitia Hédouin; Xavier Hernández-Pech; Frederique Kandel; Sherril Leon Soon; Melissa S. Roth; Lisa J. Rodrigues; Andrea G. Grottoli; Claudia Portocarrero; et al. (Coral Reefs, 2013)

Presence of Torque Teno Virus (TTV) in Tap Water in Public Schools from Southern Brazil - Andréia Dalla Vecchia; Mariana Kluge; Joseane V. dos Santos da Silva; Juliana Comerlato; Manoela T. Rodrigues; Juliane D. Fleck; Roger B. da Luz; Thais F. Teixeira; Paulo M. Roehe; Roberta Capalonga; Ana Beatriz Oliveira; Fernando R. Spilki (Food and Environmental Virology, 2013)

Organic solutes in the deepest phylogenetic branches of the Bacteria: identification of α(1–6)glucosyl-α(1–2)glucosylglycerate in Persephonella marina - Pedro Lamosa; Marta V. Rodrigues; Luís G. Gonçalves; Jean Carr; Rita Ventura; Christopher Maycock; Neil D. Raven; Helena Santos (Extremophiles, 2013)

Surviving an Invasion: Characterization of One of the Last Refugia for Artemia Diploid Parthenogenetic Strains - Carolina M. Rodrigues; Ana M. Bio; Francisco D. Amat; Nuno M. Monteiro; Natividade M. Vieira (Wetlands, 2012)

Changes in Liver Proteome Expression of Senegalese Sole (Solea senegalensis) in Response to Repeated Handling Stress - Odete D. Cordeiro; Tomé S. Silva; Ricardo N. Alves; Benjamin Costas; Tune Wulff; Nadège Richard; Mahaut de Vareilles; Luís E. C. Conceição; Pedro M. Rodrigues (Marine Biotechnology, 2012)

Isolation and Characterization of Antibacterial Compound from a Mangrove-Endophytic Fungus, Penicillium chrysogenum MTCC 5108 - Prabha Devi; Cheryl Rodrigues; C. G. Naik; L. D’Souza (Indian Journal of Microbiology, 2012)

Infective endocarditis in intravenous drug abusers: an update - C. Sousa; C. Botelho; D. Rodrigues; J. Azeredo; R. Oliveira (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Revising the M235T Polymorphism Position for the AGT Gene and Reporting a Modifying Variant in the Brazilian Population with Potential Cardiac and Neural Impact - R. R. Lemos; S. G. de Lima; J. E. Gomes da Cunha; D. F. Oliveira; M. B. Rodrigues de Souza; C. F. J. Ayres; M. F. P. M. Albuquerque; J. R. M. Oliveira (Journal of Molecular Neuroscience, 2012)

Assessment of Biotic Integrity of the Coastal Freshwater Tidal Zone of a Temperate Estuary of South America through Multiple Indicators - N. Gómez; M. Licursi; D. E. Bauer; E. S. Ambrosio; A. Rodrigues Capítulo (Estuaries and Coasts, 2012)

Occupational exposure to formaldehyde in an institute of morphology in Brazil: a comparison of area and personal sampling - Soraya de M. Ochs; Lucas de O. Grotz; Luciara S. Factorine; Mauro R. Rodrigues; Annibal D. Pereira Netto (Environmental Science and Pollution Research, 2012)

TUDCA, a Bile Acid, Attenuates Amyloid Precursor Protein Processing and Amyloid-β Deposition in APP/PS1 Mice - Ana F. Nunes; Joana D. Amaral; Adrian C. Lo; Maria B. Fonseca; Ricardo J. S. Viana; Zsuzsanna Callaerts-Vegh; Rudi D’Hooge; Cecília M. P. Rodrigues (Molecular Neurobiology, 2012)

Power law correlations in time series of wild-land and forest fires in Brazil - Luciano Rodrigues da Silva; Tatijana Stošić; Borko D. Stošić (International Journal of Remote Sensing, 2012)

The dual crop coefficient approach using a density factor to simulate the evapotranspiration of a peach orchard: SIMDualKc model versus eddy covariance measurements - T. A. Paço; M. I. Ferreira; R. D. Rosa; P. Paredes; G. C. Rodrigues; N. Conceição; C. A. Pacheco; L. S. Pereira (Irrigation Science, 2012)

Vascular endothelial growth factor-A165 (VEGF-A165) stimulates the in vitro development and oocyte competence of goat preantral follicles - V. R. Araújo; G. M. Silva; A. B. G. Duarte; D. M. Magalhães; A. P. Almeida; R. F. B. Gonçalves; J. B. Bruno; T. F. P. Silva; C. C. Campello; A. P. R. Rodrigues; J. R. Figueiredo (Cell and Tissue Research, 2011)

Analysis of the activation mechanism of Pseudomonas stutzeri cytochrome c peroxidase through an electron transfer chain - P. M. Paes de Sousa; D. Rodrigues; C. G. Timóteo; M. L. Simões Gonçalves; G. W. Pettigrew; I. Moura; J. J. G. Moura; M. M. Correia dos Santos (JBIC Journal of Biological Inorganic Chemistry, 2011)

Kanagawa-Negative, tdh- and trh-Positive Vibrio parahaemolyticus Isolated from Fresh Oysters Marketed in Fortaleza, Brazil - Regine H. S. F. Vieira; Renata A. Costa; Francisca G. R. Menezes; Giselle C. Silva; Grace N. D. Theophilo; Dália P. Rodrigues; Rodrigo Maggioni (Current Microbiology, 2011)

Evaluation of Cu potential bioavailability changes upon coastal sediment resuspension: an example on how to improve the assessment of sediment dredging environmental risks - Wilson Machado; Ana Paula C. Rodrigues; Edison D. Bidone; Silvia M. Sella; Ricardo E. Santelli (Environmental Science and Pollution Research, 2011)

Chemical characterization and synergistic antibiotic activity of volatile compounds from the essential oil of Vanillosmopsis arborea - N. K. A. Santos; H. D. M. Coutinho; G. S. B. Viana; Fabíola F. G. Rodrigues; José G. M. Costa (Medicinal Chemistry Research, 2011)

Evaluation Antimicrobial and Antiadhesive Properties of the Biosurfactant Lunasan Produced by Candida sphaerica UCP 0995 - Juliana M. Luna; Raquel D. Rufino; Leonie A. Sarubbo; Lígia R. M. Rodrigues; José A. C. Teixeira; Galba M. de Campos-Takaki (Current Microbiology, 2011)

The sensitivity of gap analysis to conservation targets - Ruppert Vimal; Ana S. L. Rodrigues; Raphaël Mathevet; John D. Thompson (Biodiversity and Conservation, 2011)

Modulation of the response to a somatosensory stimulation of the hand during the observation of manual actions - Julien I. A. Voisin; Erika C. Rodrigues; Sébastien Hétu; Philip L. Jackson; Claudia D. Vargas; Francine Malouin; C. Elaine Chapman; Catherine Mercier (Experimental Brain Research, 2011)

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

Ecophysiology parameters of four Brazilian Atlantic Forest species under shade and drought stress - Bruna D. Souza; Bruno M. Rodrigues; Laurício Endres; Mauro Guida Santos (Acta Physiologiae Plantarum, 2010)

Bacterial Communities in the Rhizosphere of Biofuel Crops Grown on Marginal Lands as Evaluated by 16S rRNA Gene Pyrosequences - Ederson da C. Jesus; Endang Susilawati; Stephanie L. Smith; Qiong Wang; Benli Chai; Ryan Farris; Jorge L. M. Rodrigues; Kurt D. Thelen; James M. Tiedje (BioEnergy Research, 2010)

Water relations and chlorophyll fluorescence responses of two leguminous trees from the Caatinga to different watering regimes - Bruna D. Souza; Marcos V. Meiado; Bruno M. Rodrigues; Mauro G. Santos (Acta Physiologiae Plantarum, 2010)

Carbon Storage in Soil Size Fractions Under Two Cacao Agroforestry Systems in Bahia, Brazil - Emanuela F. Gama-Rodrigues; P. K. Ramachandran Nair; Vimala D. Nair; Antonio C. Gama-Rodrigues; Virupax C. Baligar; Regina C. R. Machado (Environmental Management, 2010)

Butyltin levels in several Portuguese coastal areas - Pedro N. Carvalho; Pedro Nuno R. Rodrigues; M. Clara P. Basto; M. Teresa S. D. Vasconcelos (Environmental Monitoring and Assessment, 2009)

Retardation of fungal deterioration of stored soybeans by fumigation with mustard essential oil - O. D. Dhingra; G. N. Jham; F. A. Rodrigues; G. J. Silva; M. L. N. Costa (Australasian Plant Pathology, 2009)

Effect of root and foliar applications of silicon on brown spot development in rice - D. C. Rezende; F. Á. Rodrigues; V. Carré-Missio; D. A. Schurt; I. K. Kawamura; G. H. Korndörfer (Australasian Plant Pathology, 2009)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

Benefits of membrane electrodes in the electrochemistry of metalloproteins: mediated catalysis of Paracoccus pantotrophus cytochrome c peroxidase by horse cytochrome c: a case study - P. M. Paes de Sousa; S. R. Pauleta; D. Rodrigues; M. L. Simões Gonçalves; G. W. Pettigrew; I. Moura; J. J. G. Moura; M. M. Correia dos Santos (JBIC Journal of Biological Inorganic Chemistry, 2008)

A first Portuguese epidemiological survey of fungaemia in a university hospital - S. Costa-de-Oliveira; C. Pina-Vaz; D. Mendonça; A. Gonçalves Rodrigues (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Relationships among mercury, selenium, and neurochemical parameters in common loons (Gavia immer) and bald eagles (Haliaeetus leucocephalus) - A. M. Scheuhammer; N. Basu; N. M. Burgess; J. E. Elliott; G. D. Campbell; M. Wayland; L. Champoux; J. Rodrigue (Ecotoxicology, 2008)

First report of bristleworm predator of the reef octocoral Carijoa riisei - J. R. B. Souza; H. A. Rodrigues; B. M. Neves; C. D. Perez (Coral Reefs, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Water tank and numerical model studies of flow over steep smooth two-dimensional hills - J. B. R. Loureiro; D. V. Soares; J. L. A. Fontoura Rodrigues; F. T. Pinho; A. P. Silva Freire (Boundary-Layer Meteorology, 2007)

Decreased Susceptibility to Nitroimidazoles Among Bacteroides Species in Brazil - Jessica Manya B. D. Vieira; Renata F. Boente; Karla Rodrigues Miranda; Kátia E. S. Avelar; Regina M. C. P. Domingues; Maria Candida de S. Ferreira (Current Microbiology, 2006)

Modulation of endocytosis in pollen tube growth by phosphoinositides and phospholipids - D. Monteiro; P. Castanho Coelho; C. Rodrigues; L. Camacho; H. Quader; R. Malhó (Protoplasma, 2005)

Historical Evidence of Widespread Chytrid Infection in North American Amphibian Populations - MARTIN OUELLET; IGOR MIKAELIAN; BRUCE D. PAULI; JEAN RODRIGUE; DAVID M. GREEN (Conservation Biology, 2005)
Emerging infectious diseases may be contributing to the global decline of amphibian populations. In particular, chytridiomycosis, a cutaneous fungal infection of amphibians caused by the chytrid Batrachochytrium dendrobatidis , gained attention in the 1990s as an apparently new pathogen. This fungus has been implicated as the causative agent of widespread mortalities among wild amphibians in geographically disparate parts of the world. To investigate the global distribution, historical occurrence, and infectiousness of this pathogen, we examined 3371 postmetamorphic and adult amphibians collected between 1895 and 2001 from 25 countries for the presence of chytrid fungi in the epidermis. Cutaneous chytrid infection was diagnosed in 383 of 2931 (13.1%) specimens of 12 common amphibian species from five Canadian provinces and seven American states, including 30 of 69 locations examined in the St. Lawrence River Valley of Québec. Chytrids were observed in 7.0% (46/655) of the adults collected in the 1960s, the earliest cases being two green frogs ( Rana clamitans ) collected in 1961 from Saint‐Pierre‐de‐Wakefield, Québec. In recent studies, morbidity and mortality attributable to chytridiomycosis were not observed in infected amphibians from Québec despite a 17.8% (302/1698) prevalence of chytrid infection during the period 1990–2001. The prevalence of infection during this latter period was not statistically different when compared with the period 1960–1969. Epidermal chytrid infections were not observed in 440 amphibians examined from 23 other countries. In light of the fact that infection by B. dendrobatidis is widely distributed and apparently enzootic in seemingly healthy amphibians from eastern North America, lethal outbreaks of chytridiomycosis among amphibian populations appear to have complex causes and may be the result of underlying predisposing factors.

Lead Concentrations in Ruffed Grouse, Rock Ptarmigan, and Willow Ptarmiganin Québec - J Rodrigue; R McNicoll; D Leclair; J.-F Duchesne (Archives of Environmental Contamination and Toxicology, 2005)

Spatial and temporal variability in forest–atmosphere CO 2 exchange - D. Y. Hollinger; J. Aber; B. Dail; E. A. Davidson; S. M. Goltz; H. Hughes; M. Y. Leclerc; J. T. Lee; A. D. Richardson; C. Rodrigues; N.A. Scott; D. Achuatavarier; et al. (Global Change Biology, 2004)
Seven years of carbon dioxide flux measurements indicate that a ∼90‐year‐old spruce dominated forest in Maine, USA, has been sequestering 174±46 g C m −2 yr −1 (mean±1 standard deviation, nocturnal friction velocity ( u * ) threshold >0.25 m s −1 ). An analysis of monthly flux anomalies showed that above‐average spring and fall temperatures were significantly correlated with greater monthly C uptake while above‐average summer temperatures were correlated with decreased net C uptake. Summer months with significantly drier or wetter soils than normal were also characterized by lower rates of C uptake. Years with above‐average C storage were thus typically characterized by warmer than average spring and fall temperatures and adequate summer soil moisture. Environmental and forest–atmosphere flux data recorded from a second tower surrounded by similar forest, but sufficiently distant that flux source regions (‘footprints’), did not overlap significantly showed almost identical temperature and solar radiation conditions, but some differences in energy partitioning could be seen. Half‐hourly as well as integrated (annual) C exchange values recorded at the separate towers were very similar, with average annual net C uptake differing between the two towers by

Changes in Carbon Storage and Net Carbon Exchange One Year After an Initial Shelterwood Harvest at Howland Forest, ME - Neal A. Scott; Charles A. Rodrigues; Holly Hughes; John T. Lee; Eric A. Davidson; D. Bryan Dail; Phil Malerba; David Y. Hollinger (Environmental Management, 2004)

Trenching Behavior by Caterpillars of the Euphorbia Specialist, Pygarctia roseicapitis: A Field Study - E. A. Bernays; M. S. Singer; D. Rodrigues (Journal of Insect Behavior, 2004)

Chromosomal studies in Callicebus donacophilus pallescens, with classic and molecular cytogenetic approaches: Multicolour FISH using human and Saguinus oedipus painting probes - R. M. S. Barros; C. Y. Nagamachi; J. C. Pieczarka; L. R. R. Rodrigues; M. Neusser; E. H. de Oliveira; J. Wienberg; J. A. P. C. Muniz; J. D. Rissino; S. Muller (Chromosome Research, 2003)

Dam-Break Flood Emergency Management System - Armanda S. Rodrigues; Maria A. Santos; A. D. Santos; Fernanda Rocha (Water Resources Management, 2002)

The interhepatocytic macrophages and pale‐grey cells in brown trout liver ontogenesis - A. D. Resende; E. Rocha; R. A. F. Monteiro; P. Rodrigues (Journal of Fish Biology, 2002)
Pale‐grey cells appeared in the livers of healthy and non‐stressed brown trout Salmo trutta 3 weeks post‐hatching whereas interhepatocytic macrophages appeared at 5 months. Cells with intermediate morphological characteristics between those of pale‐grey cells and macrophages were identified in all ages studies. Cell ultrastructure supported the idea that pale‐grey cells probably belonged to the macrophage lineage, being eventual precursors of the active phagocytes residing amongst hepatocytes.

Associations between smoking and adenocarcinomas and squamous cell carcinomas of the uterine cervix (United States) - James V. Lacey; Morten Frisch; Louise A. Brinton; Fouad M. Abbas; Willard A. Barnes; Patti E. Gravitt; Mitchell D. Greenberg; Sarah M. Greene; Olympia C. Hadjimichael; Larry McGowan; Rodrigue Mortel; Peter E. Schwartz; et al. (Cancer Causes & Control, 2001)

Redox thermodynamics of low-potential iron-sulfur proteins - Gianantonio Battistuzzi; Mariapina D'Onofrio; Marco Borsari; Marco Sola; Anjos L. Macedo; José J. G. Moura; Pedro Rodrigues (JBIC Journal of Biological Inorganic Chemistry, 2000)

Identification of microsatellite loci in olive ( Olea europaea ) and their characterization in Italian and Iberian olive trees - K. M. Sefc; M. S. Lopes; D. Mendonça; M. Rodrigues Dos Santos; M. Laimer Da Câmara Machado; A. Da Câmara Machado (Molecular Ecology, 2000)

Contamination of local wildlife following a fire at a polychlorinated biphenyls warehouse in St Basile le Grand, Quebec, Canada - D. Phaneuf; J.L. DesGranges; N. Plante; J. Rodrigue (Archives of Environmental Contamination and Toxicology, 1995)